Laminate, optical member and optical device
A laminate with a void layer and an adhesive layer, specifically designed with a high porosity void layer and a (meth)acrylic polymer-based adhesive layer, addresses the challenge of maintaining adhesive strength and preventing adhesive penetration, even in harsh environments.
Patent Information
- Application Number
- JP2023162462
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-09-29
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2038-09-26
AI Technical Summary
The challenge is to create a laminate with a void layer and an adhesive layer that maintains adhesive strength while preventing the adhesive from penetrating into the voids, which is particularly difficult in high-temperature environments.
The laminate consists of a void layer with a porosity of 35% or more, directly laminated with an adhesive layer formed from a specific (meth)acrylic polymer and crosslinking agent. The adhesive layer has a gel fraction of 70% or more and a thickness of 2 to 50 μm, satisfying the formula (100-X)/100 × Y ≤ 10, where X is the gel fraction and Y is the thickness.
This configuration achieves both strong adhesive strength and resistance to adhesive penetration into the voids, even under high-temperature and humid conditions, while maintaining a high void remaining rate after durability testing.
Smart Images

Figure 0007662735000007 
Figure 0007662735000008 
Figure 0007662735000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, an optical member, and an optical device. [Background technology]
[0002] In optical devices, for example, an air layer with a low refractive index is used as a total reflection layer. Specifically, for example, each optical film component (for example, a light guide plate and a reflector) in a liquid crystal device is laminated via an air layer. However, if each component is separated by an air layer, problems such as bending of the component may occur, especially when the component is large. In addition, due to the trend of making devices thinner, it is desired to integrate each component. For this reason, each component is integrated with a pressure-sensitive adhesive without an air layer (for example, Patent Document 1). However, if the air layer that plays the role of total reflection is lost, optical properties such as light leakage may be deteriorated.
[0003] Therefore, it has been proposed to use a low refractive index layer instead of the air layer. For example, Patent Document 2 describes a structure in which a layer having a lower refractive index than the light guide plate is inserted between the light guide plate and the reflector plate. As the low refractive index layer, for example, a gap layer having voids is used in order to make the refractive index as close as possible to that of air. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-156082 A [Patent Document 2] Japanese Patent Application Publication No. 10-62626 Summary of the Invention [Problem to be solved by the invention]
[0005] The void layer is used by, for example, laminating it with another layer via a tacky adhesive layer. However, when the void layer and the tacky adhesive layer are laminated, the adhesive or the adhesive constituting the tacky adhesive layer may penetrate into the voids of the void layer, filling the voids, and the void ratio may decrease. The higher the void ratio of the void layer, the easier the adhesive or the adhesive will penetrate. In addition, in a high temperature environment, the adhesive or the adhesive will penetrate into the voids due to the molecular motion of the adhesive or the adhesive.
[0006] In order to suppress or prevent the pressure-sensitive adhesive or bonding agent from penetrating into the voids, the pressure-sensitive adhesive or bonding agent should have as high an elastic modulus (hardness) as possible. However, if the pressure-sensitive adhesive or bonding agent has a high elastic modulus (hardness), the adhesive strength or bonding strength may be reduced. Conversely, if the pressure-sensitive adhesive or bonding agent has a low elastic modulus (softness), it is easy to obtain high adhesive strength or bonding strength, but the pressure-sensitive adhesive or bonding agent may easily penetrate into the voids.
[0007] Therefore, an object of the present invention is to provide a laminate of a gap layer and a pressure-sensitive adhesive layer, an optical component, and an optical device that combine pressure-sensitive adhesive or bonding strength with resistance to penetration of a pressure-sensitive adhesive or adhesive into the gaps. [Means for solving the problem]
[0008] In order to achieve the above object, the first laminate of the present invention comprises: A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, The porosity of the void layer is 35% by volume or more, After a heat and humidity durability test in which the material is maintained at a temperature of 85° C. and a relative humidity of 85% for 500 hours, the remaining void ratio of the porous layer is 50% by volume or more compared to before the heat and humidity durability test.
[0009] The second laminate of the present invention is A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, The porosity of the void layer is 35% by volume or more, the pressure-sensitive adhesive layer is formed of a pressure-sensitive adhesive containing a (meth)acrylic polymer and a crosslinking agent, The gel fraction of the adhesive layer is 70% or more, The thickness of the adhesive layer is 2 to 50 μm, The adhesive layer is characterized in that it satisfies the following mathematical formula (I). [(100-X) / 100]×Y≦10 (I) In the formula (I), X is the gel fraction (%) of the adhesive layer, Y is the thickness (μm) of the adhesive layer.
[0010] The third laminate of the present invention is A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, The porosity of the void layer is 35% by volume or more, the pressure-sensitive adhesive layer is formed of a pressure-sensitive adhesive containing a (meth)acrylic polymer and a crosslinking agent, The (meth)acrylic polymer is characterized in that it is a (meth)acrylic polymer having a weight average molecular weight of 1.5 million to 2.8 million obtained by polymerizing 3 to 10 weight % of a heterocycle-containing acrylic monomer, 0.5 to 5 weight % of (meth)acrylic acid, 0.05 to 2 weight % of a hydroxyalkyl (meth)acrylate, and 83 to 96.45 weight % of an alkyl (meth)acrylate as monomer components. Note that, hereinafter, the first laminate of the present invention, the second laminate of the present invention, and the third laminate of the present invention may be collectively referred to as the "laminate of the present invention."
[0011] The optical member of the present invention is an optical member comprising the laminate of the present invention.
[0012] The optical device of the present invention is an optical device including the optical member of the present invention. Effect of the Invention
[0013] According to the present invention, it is possible to provide a laminate of a gap layer and a pressure-sensitive adhesive layer, an optical component, and an optical device that combine adhesive strength or bonding strength with resistance to penetration of a pressure-sensitive adhesive or adhesive into the gaps. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a process cross-sectional view that typically illustrates one example of a method for forming the laminate of the present invention in which a porous layer 21, an intermediate layer 22 and a tacky adhesive layer 30 are laminated on a resin film 10 in the present invention. [Diagram 2] FIG. 2 is a diagram that illustrates a part of the steps in the method for producing a roll-shaped laminated film (laminate film roll) and an example of an apparatus used therein. [Diagram 3] FIG. 3 is a diagram illustrating a part of the steps in the method for producing a laminated film roll and another example of an apparatus used therein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following description in any way.
[0016] The first laminate of the present invention may, for example, have a void remaining rate of the void layer after the heat and humid durability test that is greater than 50% and not more than 99% of the void remaining rate when only the void layer is subjected to the heat and humid durability test.
[0017] The first laminate of the present invention is, for example, The void layer and the adhesive layer are laminated via an intermediate layer, The intermediate layer is a layer formed by combining a part of the void layer and a part of the adhesive layer, The thickness of the intermediate layer is 200 nm or less, After the heat and humidity durability test, an increase in thickness of the intermediate layer may be 500% or less relative to the thickness of the intermediate layer before the heat and humidity durability test.
[0018] As described above, the second laminate of the present invention has a value of [(100-X) / 100]×Y represented by the formula (I) of 10 or less. This means that the amount of components in the adhesive layer that penetrate into the void layer is small. This can suppress or prevent the phenomenon in which the voids in the void layer are filled and the porosity is reduced. The gel fraction (X) of the adhesive is 70% or more as described above, and may be, for example, 75% or more or 80% or more. The upper limit of the gel fraction (X) is not particularly limited, and may be, for example, 100% or less or 95% or less. The gel fraction (X) of the adhesive may be, for example, 75 to 95% or 80 to 95%. The thickness (Y) of the adhesive layer is 2 to 50 μm as described above, and may be, for example, 5 μm or more or 10 μm or more, and may be, for example, 40 μm or less or 30 μm or less. The thickness (Y) of the adhesive layer may be, for example, 5 to 40 μm or 10 to 30 μm.
[0019] The method for measuring the gel fraction (X) of the adhesive layer is not particularly limited, but may be, for example, the method described in the Examples below. The method for measuring the thickness (Y) of the adhesive layer is not particularly limited, but may be, for example, the method described in the Examples below.
[0020] In the second laminate of the present invention, by setting the gel fraction (X) of the adhesive layer, the thickness (Y) of the adhesive layer, and [(100-X) / 100]×Y represented by the formula (I) within the above-mentioned specific ranges, it is possible to provide a laminate of a void layer and an adhesive layer, an optical component, and an optical device which achieve both adhesive strength or bonding strength and resistance to penetration of the adhesive into the voids.
[0021] In the second laminate of the present invention, for example, in a molecular weight measurement of the adhesive layer by gel permeation chromatography, the weight average molecular weight of the sol component of the adhesive layer may be 50,000 to 500,000. In addition, for example, in a molecular weight measurement of the adhesive layer by gel permeation chromatography, the content of low molecular weight components having a molecular weight of 10,000 or less in the sol component of the adhesive layer may be 20% by weight (mass%) or less. By setting the weight average molecular weight of the sol component or the content of low molecular weight components having a molecular weight of 10,000 or less in the sol component to the specific range, the pressure-sensitive adhesive is further less likely to penetrate into the voids of the void layer. The weight average molecular weight of the sol component may be, for example, 70,000 or more, for example, 450,000 or less or 400,000 or less, for example, 70 to 450,000 or 70 to 400,000. In addition, the content (ratio) of components having a molecular weight of 10,000 or less in the sol component may be, for example, 20% by weight or less, as described above, with respect to the total amount (100% by weight) of the sol component, for example, 15% by weight or less or 10% by weight or less. The lower limit of the content (ratio) of the component having a molecular weight of 10,000 or less in the sol fraction is not particularly limited, but may be, for example, 0% by weight or more or a value exceeding 0% by weight, for example, 3% by weight or more. The content (ratio) of the component having a molecular weight of 10,000 or less in the sol fraction may be, for example, 3 to 15% by weight or 3 to 10% by weight.
[0022] The specific measurement method by gel permeation chromatography is not particularly limited, and may be, for example, the measurement method described in the examples below.
[0023] The second or third laminate of the present invention may have a void remaining rate of 50 volume % or more of the void remaining rate before the heat and humidity durability test, for example, after a heat and humidity durability test in which the laminate is maintained at a temperature of 85° C. and a relative humidity of 85% for 500 hours. The second or third laminate of the present invention may have a void remaining rate of 50 volume % or more of the void remaining rate before the heat and humidity durability test, for example, of more than 50% and 99% or less of the void remaining rate when only the void layer is subjected to the heat and humidity durability test.
[0024] The second or third laminate of the present invention is, for example, The void layer and the adhesive layer are laminated via an intermediate layer, The intermediate layer is a layer formed by combining a part of the void layer and a part of the adhesive layer, The intermediate layer may have a thickness of 200 nm or less.
[0025] The second or third laminate of the present invention may, for example, after a heat and humidity durability test in which the intermediate layer is maintained at a temperature of 85°C and a relative humidity of 85% for 500 hours, the increase in thickness of the intermediate layer may be 500% or less compared to the thickness of the intermediate layer before the heat and humidity durability test.
[0026] In the laminate of the present invention, for example, the refractive index of the porous layer may be 1.25 or less.
[0027] In the laminate of the present invention, for example, the adhesive layer may be formed of an optical acrylic adhesive having a total light transmittance of 85% or more and a haze of 3% or less. The total light transmittance and haze of the adhesive layer may be measured by the same measuring method as that of the laminate or the porous layer described later.
[0028] The laminate of the present invention may have a storage modulus of the adhesive layer at 23° C. of, for example, 1.0×10 5 The method for measuring the storage modulus at 23° C. is not particularly limited, but it can be measured, for example, by the measurement method described in the Examples below.
[0029] In the second or third laminate of the present invention, the adhesive layer is formed of an adhesive containing a (meth)acrylic polymer and a crosslinking agent, as described above. In the adhesive layer, for example, the (meth)acrylic polymer may be crosslinked by the crosslinking agent to form a crosslinked structure.
[0030] In the laminate of the present invention, the reason (mechanism) that both the adhesive force or bonding force and the difficulty of the adhesive or adhesive penetrating into the voids can be achieved is, for example, as follows. For example, by forming a tacky adhesive layer using a specific adhesive, both the adhesive force or bonding force and the difficulty of the adhesive or adhesive penetrating into the voids can be achieved. More specifically, for example, by forming a tacky adhesive layer using the specific adhesive as described above, an intermediate layer is formed by merging a part of the void layer with a part of the tacky adhesive layer. And, by using the specific adhesive as described above, the intermediate layer does not spread excessively even under conditions such as the heat and humidity durability test. In addition, the intermediate layer acts as a stopper, and the decrease in porosity caused by the voids in the void layer being filled with the adhesive can be suppressed. Even if the molecular motion of the adhesive increases under heating, if the elastic modulus of the adhesive is high, the intermediate layer formed from the adhesive and the high void layer is likely to become a strong and dense stopper, and the penetration of the adhesive into the high void layer is suppressed. However, these mechanisms are merely examples and do not limit the present invention in any way.
[0031] [1. Laminate, optical member, and optical device] As described above, the laminate of the present invention includes a void layer and a tacky adhesive layer, and the tacky adhesive layer is directly laminated on one or both sides of the void layer. In the present invention, the tacky adhesive layer is "directly laminated" on the void layer, which may mean that the tacky adhesive layer is in direct contact with the void layer, or the tacky adhesive layer is laminated on the void layer via the intermediate layer.
[0032] In the laminate of the present invention, after a heat and humidity durability test in which the laminate is maintained at a temperature of 85°C and a relative humidity of 85% for 500 hours, the remaining void ratio of the porous layer may be, for example, 50 volume % or more, 55 volume % or more, or 60 volume % or more, relative to the voids before the heat and humidity durability test.The upper limit is not particularly limited, but is ideally 100 volume %, and may be 99 volume % or less, 98 volume % or less, or 95 volume % or less.
[0033] When the laminate of the present invention has the intermediate layer, as described above, for example, after a heat and humidity durability test in which the intermediate layer is held at a temperature of 85° C. and a relative humidity of 85% for 500 hours, the increase rate of the thickness of the intermediate layer may be 500% or less, when the thickness of the intermediate layer before the heat and humidity durability test is 100%, relative to the thickness of the intermediate layer before the heat and humidity durability test. The increase rate of the thickness of the intermediate layer after the heat and humidity durability test may be, for example, 400% or less, 350% or less, or 300% or less, when the thickness of the intermediate layer before the heat and humidity durability test is 100%, relative to the thickness of the intermediate layer before the heat and humidity durability test, and may be, for example, 100% or more, 110% or more, 120% or more, 130% or more, or 140% or more.
[0034] Furthermore, in the laminate of the present invention, the void remaining rate of the void layer after the heat and humid durability test may be, for example, as described above, more than 50% and not more than 99% of the void remaining rate when only the void layer is subjected to the heat and humid durability test, or may be 53% or more, 55% or more, or 60% or more, or may be 98% or less, 97% or less, or 96% or less.
[0035] The laminate of the present invention may have a light transmittance of 80% or more for the laminate of the adhesive layer and the void layer, or the laminate of the adhesive layer, the intermediate layer and the void layer. The laminate may have a haze of 3% or less for example. The light transmittance may be, for example, 82% or more, 84% or more, 86% or more, or 88% or more, and the upper limit is not particularly limited, but is ideally 100%, and may be, for example, 95% or less, 92% or less, 91% or less, or 90% or less. The haze of the laminate may be measured, for example, by the same method as the measurement of the haze of the void layer described later. The light transmittance is the transmittance of light with a wavelength of 550 nm, and may be measured, for example, by the following measurement method.
[0036] (Method of measuring light transmittance) The laminate is treated as a sample to be measured using a spectrophotometer U-4100 (trade name of Hitachi, Ltd.). The total light transmittance (light transmittance) of the sample is measured when the total light transmittance of air is taken as 100%. The total light transmittance (light transmittance) value is taken as the value measured at a wavelength of 550 nm.
[0037] In the laminate of the present invention, for example, the adhesive strength or adhesion of the adhesive layer may be, for example, 0.7N / 25mm or more, 0.8N / 25mm or more, 1.0N / 25mm or more, or 1.5N / 25mm or more, or 50N / 25mm or less, 30N / 25mm or less, 10N / 25mm or less, 5N / 25mm or less, or 3N / 25mm or less. From the viewpoint of the risk of peeling during handling when the laminate is attached to another layer, it is preferable that the adhesive strength or adhesion of the adhesive layer is not too low. In addition, from the viewpoint of rework when reattaching, it is preferable that the adhesive strength or adhesion of the adhesive layer is not too high. The adhesive strength or adhesion of the adhesive layer can be measured, for example, as follows.
[0038] (Method of measuring adhesive strength or adhesion) The laminated film of the present invention (the laminated body of the present invention formed on a resin film substrate) is sampled in a strip shape of 50 mm x 140 mm, and the sample is fixed to a stainless steel plate with double-sided tape. An acrylic adhesive layer (thickness 20 μm) is attached to a PET film (T100: manufactured by Mitsubishi Plastics Film Co., Ltd.), and an adhesive tape piece cut to 25 mm x 100 mm is attached to the opposite side of the laminated film of the present invention to the resin film, and laminated with the PET film. Next, the sample is chucked in an autograph tensile tester (manufactured by Shimadzu Corporation: AG-Xplus) so that the chuck distance is 100 mm, and then a tensile test is performed at a tensile speed of 0.3 m / min. The average test force obtained by performing a 50 mm peel test is the adhesive peel strength, i.e., the adhesive force. The adhesive force can also be measured by the same measurement method. In the present invention, there is no clear distinction between "adhesive force" and "adhesive force".
[0039] The laminate of the present invention may be formed on a substrate such as a film. The film may be a resin film. Generally, a relatively thin one may be called a "film" and a relatively thick one may be called a "sheet", but in the present invention, there is no particular distinction between the "film" and the "sheet".
[0040] The substrate is not particularly limited, and for example, a substrate made of a thermoplastic resin, a substrate made of glass, an inorganic substrate such as silicon, a plastic molded from a thermosetting resin, an element such as a semiconductor, a carbon fiber material such as a carbon nanotube, etc. can be preferably used, but is not limited thereto. The form of the substrate can be, for example, a film, a plate, etc. Examples of the thermoplastic resin include polyethylene terephthalate (PET), acrylic, cellulose acetate propionate (CAP), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), etc.
[0041] The optical member of the present invention is not particularly limited, and may be, for example, an optical film including the laminate of the present invention.
[0042] The optical apparatus (optical device) of the present invention is not particularly limited, and may be, for example, an image display apparatus or a lighting apparatus. Examples of the image display apparatus include a liquid crystal display, an organic EL (Electro Luminescence) display, and a micro LED (Light Emitting Diode) display. Examples of the lighting apparatus include an organic EL lighting apparatus.
[0043] [2.Void layer] The void layer in the laminate of the present invention (hereinafter, sometimes referred to as the "void layer of the present invention") will be described below by way of examples, although the void layer of the present invention is not limited thereto.
[0044] The porous layer of the present invention may have a porosity of 35 volume % or more and a peak pore size of 50 nm or less, for example, although this is merely an example and the porous layer of the present invention is not limited thereto.
[0045] The porosity may be, for example, 35% by volume or more, 38% by volume or more, or 40% by volume or more, and may be 90% by volume or less, 80% by volume or less, or 75% by volume or less. The porous layer of the present invention may be, for example, a highly porous layer having a porosity of 60% by volume or more.
[0046] The porosity can be measured, for example, by the following measurement method.
[0047] (Method of measuring void ratio) If the layer to be measured for porosity is a single layer containing voids, the ratio (volume ratio) of the constituent material of the layer to air can be calculated by a standard method (e.g., measuring the weight and volume to calculate the density), and the porosity (volume %) can be calculated from this. In addition, since there is a correlation between the refractive index and the porosity, it is also possible to calculate the porosity from the refractive index value of the layer, for example. Specifically, the porosity is calculated from the refractive index value measured by an ellipsometer using the Lorentz-Lorenz's formula.
[0048] The porous layer of the present invention can be produced, for example, by chemically bonding pulverized gel (microporous particles) as described below. In this case, the pores in the porous layer can be conveniently divided into the following three types (1) to (3). (1) Voids in the raw gel itself (within the particles) (2) Voids in the gel pulverized material units (3) Gaps between the gel particles caused by accumulation of the gel particles
[0049] The voids (2) are voids formed during pulverization in addition to the voids (1) that may be formed in each block when each particle group produced by pulverizing the gel is regarded as a single block, regardless of the size, dimensions, etc. of the pulverized gel product (microporous particles). The voids (3) are voids that are generated during pulverization (e.g., media-less pulverization, etc.) because the size, dimensions, etc. of the pulverized gel product (microporous particles) become non-uniform. The porous layer of the present invention has, for example, the voids (1) to (3) described above, and thus has an appropriate porosity and peak pore size.
[0050] The peak pore diameter may be, for example, 5 nm or more, 10 nm or more, or 20 nm or more, or 50 nm or less, 40 nm or less, or 30 nm or less. If the peak pore diameter is too large in the porous layer when the porosity is high, the light is scattered and the layer becomes opaque. In the present invention, the lower limit of the peak pore diameter of the porous layer is not particularly limited, but if the peak pore diameter is too small, it is difficult to increase the porosity, so it is preferable that the peak pore diameter is not too small. In the present invention, the peak pore diameter can be measured, for example, by the following method.
[0051] (Method of measuring peak pore diameter) A pore distribution / specific surface area measuring device (BELLSORP MINI / product name of Microtrack Bell Co., Ltd.) is used to calculate the peak pore diameter from the results of calculating the BJH plot and BET plot by nitrogen adsorption and the isothermal adsorption curve.
[0052] Furthermore, the thickness of the porous layer of the present invention is not particularly limited, and may be, for example, 100 nm or more, 200 nm or more, or 300 nm or more, and may be 10,000 nm or less, 5,000 nm or less, or 2,000 nm or less.
[0053] In the void layer of the present invention, for example, as described later, by using a pulverized product of a porous gel, the three-dimensional structure of the porous gel is destroyed, and a new three-dimensional structure different from the porous gel is formed. In this way, the void layer of the present invention is a layer in which a new pore structure (new void structure) that cannot be obtained in a layer formed from the porous gel is formed, and thus a nanoscale void layer with high porosity can be formed. In addition, in the case where the void layer of the present invention is, for example, a silicone porous body, the pulverized products are chemically bonded to each other while adjusting the number of siloxane bond functional groups of the silicon compound gel. In addition, since a new three-dimensional structure is formed as a precursor of the void layer, and then chemically bonded (for example, crosslinked) in a bonding process, the void layer of the present invention has a structure having voids, but can maintain sufficient strength and flexibility, for example, when the void layer is a functional porous body. Therefore, according to the present invention, the void layer can be easily and simply applied to various objects.
[0054] The void layer of the present invention contains, for example, pulverized porous gel, and the pulverized materials are chemically bonded to each other, as described below. In the void layer of the present invention, the form of chemical bonding (chemical bond) between the pulverized materials is not particularly limited, and specific examples of the chemical bond include cross-linking. The method of chemically bonding the pulverized materials to each other is, for example, as described in detail in the manufacturing method of the void layer described above.
[0055] The crosslinked bond is, for example, a siloxane bond. Examples of the siloxane bond include the following T2 bond, T3 bond, and T4 bond. When the silicone porous body of the present invention has a siloxane bond, it may have, for example, any one type of bond, any two types of bonds, or all three types of bonds. The higher the ratio of T2 and T3 among the siloxane bonds, the more flexible the gel is, and the gel's inherent properties can be expected, but the film strength becomes weak. On the other hand, when the ratio of T4 among the siloxane bonds is high, the film strength is easily expressed, but the void size becomes small and the flexibility becomes weak. For this reason, it is preferable to change the ratio of T2, T3, and T4 depending on the application, for example.
[0056] [ka]
[0057] When the porous layer of the present invention has the siloxane bond, the ratio of T2, T3 and T4, when expressed relatively with T2 being "1", is, for example, T2:T3:T4=1:[1-100]:[0-50], 1:[1-80]:[1-40], 1:[5-60]:[1-30].
[0058] In addition, in the porous layer of the present invention, for example, the silicon atoms contained therein are preferably siloxane-bonded.Specifically, the ratio of unbonded silicon atoms (i.e., residual silanol) to all silicon atoms contained in the silicone porous body is, for example, less than 50%, 30% or less, or 15% or less.
[0059] The void layer of the present invention has, for example, a pore structure. In the present invention, the void size of the pores refers to the diameter of the long axis of the voids (holes) among the diameter of the long axis and the diameter of the short axis. The pore size is, for example, 5 nm to 50 nm. The lower limit of the void size is, for example, 5 nm or more, 10 nm or more, or 20 nm or more, and the upper limit is, for example, 50 nm or less, 40 nm or less, or 30 nm or less, and the range is, for example, 5 nm to 50 nm, or 10 nm to 40 nm. The preferred void size is determined depending on the application of the void structure, so it is necessary to adjust the void size to a desired void size depending on the purpose, for example. The void size can be evaluated, for example, by the following method.
[0060] (Cross-sectional SEM observation of void layer) In the present invention, the morphology of the void layer can be observed and analyzed using a SEM (scanning electron microscope). Specifically, for example, the void layer is subjected to FIB processing (accelerating voltage: 30 kV) under cooling, and a cross-sectional sample obtained can be subjected to FIB-SEM (manufactured by FEI: product name Helios NanoLab600, accelerating voltage: 1 kV) to obtain a cross-sectional electron image at an observation magnification of 100,000 times.
[0061] (Evaluation of void size) In the present invention, the pore size can be quantified by the BET test method. Specifically, 0.1 g of a sample (porous layer of the present invention) is placed in the capillary of a pore distribution / specific surface area measuring device (BELLSORP MINI / product name of Microtrack Bell Co., Ltd.), and then dried under reduced pressure at room temperature for 24 hours to remove the gas from the pore structure. Then, nitrogen gas is adsorbed onto the sample, and a BET plot, a BJH plot, and an adsorption isotherm are drawn to determine the pore distribution. This allows the pore size to be evaluated.
[0062] In the porous layer of the present invention, the film density indicating the porosity is not particularly limited, and the lower limit is, for example, 1 g / cm 3 More than 5g / cm 3 More than 10g / cm 3 More than 15g / cm 3 or more, and the upper limit is, for example, 50 g / cm 3 Below 40g / cm 3 Below 30g / cm 3 Below, 2.1g / cm 3 The range is, for example, 5 to 50 g / cm 3 , 10~40g / cm 3 , 15~30g / cm 3 , 1~2.1g / cm 3 It is.
[0063] The film density can be measured, for example, by the following method.
[0064] (Evaluation of film density) After forming a void layer (void layer of the present invention) on an acrylic film, the X-ray reflectance in the total reflection region was measured using an X-ray diffractometer (RIGAKU: RINT-2000). After fitting the intensity and 2θ, the porosity (P%) was calculated from the total reflection critical angle of the void layer and substrate. The film density can be expressed by the following formula. Membrane density (%)=100(%)-Porosity (P%)
[0065] The void layer of the present invention may have a pore structure (porous structure) as described above, and may be, for example, an open-cell structure in which the pore structure is continuous. The open-cell structure means, for example, that the pore structure is three-dimensionally connected in the void layer, and can also be said to be a state in which the internal voids of the pore structure are continuous. When the porous body has an open-cell structure, it is possible to increase the porosity in the bulk, but when closed-cell particles such as hollow silica are used, an open-cell structure cannot be formed. In contrast, the void layer of the present invention has a three-dimensional dendritic structure in which the dendritic particles settle and deposit in the coating film (coating film of the sol containing the pulverized porous gel), and therefore the open-cell structure can be easily formed. In addition, it is more preferable that the void layer of the present invention forms a monolith structure in which the open-cell structure has a plurality of pore distributions. The monolith structure refers to, for example, a structure in which fine nano-sized voids exist and a hierarchical structure in which the nano-voids are aggregated and exist as an open-cell structure. When forming the monolithic structure, for example, it is possible to achieve both membrane strength and high porosity by imparting membrane strength with fine pores and high porosity with coarse open-cell pores. To form such a monolithic structure, for example, it is important to first control the pore distribution of the pore structure to be generated in the porous gel prior to pulverization into the pulverized material. In addition, for example, when pulverizing the porous gel, the particle size distribution of the pulverized material can be controlled to a desired size to form the monolithic structure.
[0066] In the air gap layer of the present invention, the haze indicating transparency is not particularly limited, and the lower limit is, for example, 0.1% or more, 0.2% or more, or 0.3% or more, and the upper limit is, for example, 10% or less, 5% or less, or 3% or less, and the range is, for example, 0.1 to 10%, 0.2 to 5%, or 0.3 to 3%.
[0067] The haze can be measured, for example, by the following method.
[0068] (Hayes's rating) The porous layer (porous layer of the present invention) is cut to a size of 50 mm x 50 mm, and is set in a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) to measure the haze. The haze value is calculated according to the following formula. Haze (%) = [Diffuse transmittance (%) / Total light transmittance (%)] x 100 (%)
[0069] The refractive index is generally the ratio of the transmission speed of the wavefront of light in vacuum to the propagation speed in the medium, and is called the refractive index of the medium. The refractive index of the air gap layer of the present invention is not particularly limited, and its upper limit is, for example, 1.3 or less, less than 1.3, 1.25 or less, 1.2 or less, 1.15 or less, its lower limit is, for example, 1.05 or more, 1.06 or more, 1.07 or more, and its range is, for example, 1.05 or more and 1.3 or less, 1.05 or more and 1.3 or less, 1.05 or more and 1.25 or less, 1.06 or more and 1.2 or less, 1.07 or more and 1.15 or less.
[0070] In the present invention, the refractive index is measured at a wavelength of 550 nm unless otherwise specified. The method for measuring the refractive index is not particularly limited, and can be, for example, measured by the following method.
[0071] (Refractive index evaluation) After forming a void layer (void layer of the present invention) on an acrylic film, cut it to a size of 50 mm x 50 mm and attach it to the surface of a glass plate (thickness: 3 mm) with an adhesive layer. The center of the back surface of the glass plate (diameter: about 20 mm) is painted with black ink to prepare a sample that does not reflect on the back surface of the glass plate. The sample is set in an ellipsometer (JA Woollam Japan: VASE) and the refractive index is measured under conditions of a wavelength of 500 nm and an incident angle of 50 to 80 degrees, and the average value is taken as the refractive index.
[0072] The thickness of the porous layer of the present invention is not particularly limited, and the lower limit is, for example, 0.05 μm or more, 0.1 μm or more, and the upper limit is, for example, 1000 μm or less, 100 μm or less, and the range is, for example, 0.05 to 1000 μm, 0.1 to 100 μm.
[0073] The form of the porous layer of the present invention is not particularly limited, and may be, for example, a film shape or a block shape.
[0074] The method for producing the porous layer of the present invention is not particularly limited, and for example, the porous layer can be produced by the production method described below.
[0075] [3. Adhesive] In the laminate of the present invention, the adhesive layer can be formed, for example, using at least one of a pressure-sensitive adhesive and an adhesive. In the present invention, the "pressure-sensitive adhesive" and the "adhesive" are not necessarily clearly distinguishable from each other, as described later. The pressure-sensitive adhesive is not particularly limited, but examples thereof include the pressure-sensitive adhesives exemplified below.
[0076] The adhesive used to form the adhesive layer in the laminate of the present invention uses as a base polymer, for example, a (meth)acrylic polymer having, as monomer components, 3 to 10 wt % of a heterocycle-containing acrylic monomer, a polymerizable functional group, 0.5 to 5 wt % of (meth)acrylic acid, 0.05 to 2 wt % of a hydroxyalkyl (meth)acrylate, and 83 to 96.45 wt % of an alkyl (meth)acrylate.
[0077] As the heterocycle-containing acrylic monomer, for example, one having a polymerizable functional group and a heterocycle can be used without any particular limitation. Examples of the polymerizable functional group include a (meth)acryloyl group and a vinyl ether group. Among these, a (meth)acryloyl group is preferred. Examples of the heterocycle include a morpholine ring, a piperidine ring, a pyrrolidine ring, and a piperazine ring. Examples of the heterocycle-containing acrylic monomer include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine. Among these, N-acryloylmorpholine is preferred. In addition, the heterocycle-containing acrylic monomer can improve the durability of both heat resistance and moisture resistance when the pressure-sensitive adhesive layer is thinned.
[0078] In addition, the heterocycle-containing acrylic monomer is preferred in that it can improve the adhesive strength of the pressure-sensitive adhesive layer to the optical film, particularly in that it can improve the adhesive strength to cyclic polyolefins such as norbornene-based resins, and is suitable when cyclic polyolefins are used as the optical film.
[0079] The heterocycle-containing acrylic monomer is used, for example, at a ratio of 3 to 10% by weight based on the total amount of monomer components forming the (meth)acrylic polymer. The ratio of the heterocycle-containing acrylic monomer may be, for example, 4 to 9.5% by weight or 6 to 9% by weight. The ratio of the heterocycle-containing acrylic monomer is preferably not less than the above range from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer is thinned. In addition, the ratio of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of moisture resistance when the pressure-sensitive adhesive layer is thinned. In addition, the ratio of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of improving the adhesion of the pressure-sensitive adhesive layer. In addition, the ratio of the heterocycle-containing acrylic monomer is preferably not more than the above range from the viewpoint of adhesive strength.
[0080] As the (meth)acrylic acid, acrylic acid is particularly preferred.
[0081] The (meth)acrylic acid is used, for example, at a ratio of 0.5 to 5% by weight based on the total amount of monomer components forming the (meth)acrylic polymer. The ratio of (meth)acrylic acid may be, for example, 1 to 4.5% by weight or 1.5 to 4% by weight. The ratio of (meth)acrylic acid is preferably not less than the above range from the viewpoint of heat resistance when the pressure-sensitive adhesive layer (adhesive layer) is thinned. Moreover, the ratio of (meth)acrylic acid is preferably not more than the above range from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer is thinned. Moreover, the ratio of (meth)acrylic acid is preferably not more than the above range from the viewpoint of adhesive strength.
[0082] As the hydroxyalkyl (meth)acrylate, for example, those having a polymerizable functional group and a hydroxyl group can be used without any particular limitation.As the hydroxyalkyl (meth)acrylate, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, etc. are suitable.
[0083] The hydroxyalkyl (meth)acrylate is used, for example, at a ratio of 0.05 to 2% by weight based on the total amount of monomer components forming the (meth)acrylic polymer. The ratio of the hydroxyalkyl (meth)acrylate may be, for example, 0.075 to 1.5% by weight or 0.1 to 1% by weight. The ratio of the hydroxyalkyl (meth)acrylate is preferably not less than the above range from the viewpoint of heat resistance when the adhesive layer (adhesive layer) is thinned. In addition, the ratio of the hydroxyalkyl (meth)acrylate is preferably not more than the above range from the viewpoint of heat resistance and moisture resistance when the adhesive layer is thinned. In addition, the ratio of the hydroxyalkyl (meth)acrylate is preferably not more than the above range from the viewpoint of adhesive strength.
[0084] The alkyl (meth)acrylate may have an average carbon number of about 1 to 12 in the alkyl group of the alkyl (meth)acrylate. The (meth)acrylate refers to acrylate and / or methacrylate, and (meth) in the present invention has the same meaning. Specific examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, etc., which can be used alone or in combination. Among these, alkyl (meth)acrylates having an alkyl group with 1 to 9 carbon atoms are preferred.
[0085] The alkyl (meth)acrylate is used in an amount of, for example, 83 to 96.45% by weight based on the total amount of monomer components forming the (meth)acrylic polymer. The alkyl (meth)acrylate is usually the remainder other than the heterocycle-containing acrylic monomer, (meth)acrylic acid, and hydroxyalkyl (meth)acrylate.
[0086] As the monomer components forming the (meth)acrylic polymer, for example, in addition to the above-mentioned monomers, any other monomers can be used in an amount of 10% or less of the total amount of monomers, as long as the object of the present invention is not impaired.
[0087] Examples of the optional monomer include acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride, caprolactone adducts of acrylic acid, sulfonic acid group-containing monomers such as styrene sulfonic acid, allyl sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid, and phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate. Nitrogen-containing vinyl monomers are also included. For example, maleimide, N-cyclohexylmaleimide, N-phenylmaleimide; (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methylolpropane(meth)acrylamide and other (N-substituted) amide monomers; aminoethyl(meth)acrylate, aminopropyl(meth)acrylate, N,N(meth)acrylic acid -dimethylaminoethyl, t-butylaminoethyl (meth)acrylate, 3-(3-pyridyl)propyl (meth)acrylate and other alkylaminoalkyl (meth)acrylate monomers; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate and other alkoxyalkyl (meth)acrylate monomers; and succinimide monomers such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyoctamethylene succinimide.
[0088] Furthermore, vinyl monomers such as vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinylcaprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; and acrylic ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl acrylate can also be used.
[0089] Further, as copolymerizable monomers other than the above, there may be mentioned silane-based monomers containing silicon atoms, etc. Examples of the silane-based monomers include 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc.
[0090] The (meth)acrylic polymer used in the present invention may have a weight average molecular weight of, for example, 1.5 million to 2.8 million. The weight average molecular weight may be, for example, 1.7 million to 2.7 million or 2 million to 2.5 million. The weight average molecular weight is preferably not smaller than the above range from the viewpoint of heat resistance and moisture resistance when the pressure-sensitive adhesive layer is thinned. In addition, the weight average molecular weight is preferably not larger than the above range from the viewpoint of durability, lamination property, and adhesive strength when the pressure-sensitive adhesive layer is thinned. In the present invention, the weight average molecular weight refers to a value measured by, for example, GPC (gel permeation chromatography) and calculated in terms of polystyrene.
[0091] The method for producing such a (meth)acrylic polymer is not particularly limited, and can be appropriately selected from known production methods such as solution polymerization, bulk polymerization, emulsion polymerization, various radical polymerizations, etc. The obtained (meth)acrylic polymer may be any of a random copolymer, a block copolymer, a graft copolymer, etc.
[0092] In the solution polymerization, for example, ethyl acetate, toluene, etc. are used as a polymerization solvent. In a specific example of the solution polymerization, the reaction is carried out under a stream of an inert gas such as nitrogen, with the addition of a polymerization initiator, at a temperature of about 50 to 70° C., for about 5 to 30 hours.
[0093] The polymerization initiator, chain transfer agent, emulsifier, etc. used in the radical polymerization are not particularly limited and can be appropriately selected and used. The weight average molecular weight of the (meth)acrylic polymer can be controlled by the amount of the polymerization initiator and chain transfer agent used and the reaction conditions, and the amount used is appropriately adjusted depending on the type of these.
[0094] Examples of the polymerization initiator include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.); persulfates such as potassium persulfate and ammonium persulfate; di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butyl ... Examples of the initiator include, but are not limited to, peroxide initiators such as dicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, t-butyl peroxypivalate, dilauroyl peroxide, di-n-octanoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, t-butyl peroxyisobutyrate, 1,1-di(t-hexylperoxy)cyclohexane, t-butyl hydroperoxide, and hydrogen peroxide; and redox initiators combining a peroxide and a reducing agent, such as a combination of a persulfate and sodium hydrogen sulfite, or a combination of a peroxide and sodium ascorbate.
[0095] The polymerization initiator may be used alone or in combination of two or more. The total content of the polymerization initiator may be, for example, about 0.005 to 1 part by weight or about 0.02 to 0.5 part by weight based on 100 parts by weight of the monomer.
[0096] In addition, when a (meth)acrylic polymer having the above weight average molecular weight is produced using, for example, 2,2'-azobisisobutyronitrile as a polymerization initiator, the amount of the polymerization initiator used may be, for example, about 0.06 to 0.2 parts by weight or about 0.08 to 0.175 parts by weight relative to 100 parts by weight of the total amount of the monomer components.
[0097] Examples of the chain transfer agent include lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol. The chain transfer agent may be used alone or in combination of two or more. The total content of the chain transfer agent is, for example, about 0.1 parts by weight or less relative to 100 parts by weight of the total amount of the monomer components.
[0098] Examples of emulsifiers used in emulsion polymerization include anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, polyoxyethylene alkyl ether ammonium sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate, and nonionic emulsifiers such as polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, and polyoxyethylene-polyoxypropylene block polymer. These emulsifiers may be used alone or in combination of two or more.
[0099] Furthermore, as reactive emulsifiers, emulsifiers having radical polymerizable functional groups such as propenyl groups and allyl ether groups are specifically exemplified by Aqualon HS-10, HS-20, KH-10, BC-05, BC-10, and BC-20 (all manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and Adeka Reasoap SE10N (manufactured by Asahi Denka Kogyo Co., Ltd.). Reactive emulsifiers are preferred because they are incorporated into the polymer chain after polymerization, improving water resistance. The amount of emulsifier used is 0.3 to 5 parts by weight, and more preferably 0.5 to 1 part by weight, based on 100 parts by weight of the total amount of monomer components, in terms of polymerization stability and mechanical stability.
[0100] The adhesive is preferably an adhesive composition containing a crosslinking agent. Examples of polyfunctional compounds that can be blended into the adhesive include organic crosslinking agents and polyfunctional metal chelates. Examples of organic crosslinking agents include epoxy crosslinking agents, isocyanate crosslinking agents, and imine crosslinking agents. Examples of organic crosslinking agents are isocyanate crosslinking agents. The polyfunctional metal chelate is a polyvalent metal covalently or coordinately bonded to an organic compound. Examples of polyvalent metal atoms include Al, Cr, Zr, Co, Cu, Fe, Ni, V, Zn, In, Ca, Mg, Mn, Y, Ce, Sr, Ba, Mo, La, Sn, and Ti. Examples of atoms in the organic compound that are covalently or coordinately bonded include oxygen atoms, and examples of organic compounds include alkyl esters, alcohol compounds, carboxylic acid compounds, ether compounds, and ketone compounds.
[0101] Examples of the isocyanate crosslinking agent include aromatic isocyanates such as tolylene diisocyanate and xylylene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate, and aliphatic isocyanates such as hexamethylene diisocyanate.
[0102] More specifically, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate, alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate and isophorone diisocyanate, aromatic diisocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate and polymethylene polyphenyl isocyanate, trimethylolpropane / tolylene diisocyanate trimer adduct (Nippon Polyurethane Industry Co., Ltd.) Examples of such polyisocyanates include isocyanate adducts such as a trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate L), a trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate HL), and an isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., product name: Coronate HX); polyether polyisocyanates, polyester polyisocyanates, and adducts of these with various polyols; and polyisocyanates which have been multifunctionalized with an isocyanurate bond, a biuret bond, an allophanate bond, or the like.
[0103] The isocyanate-based crosslinking agent may be used alone or in combination of two or more, and the total content may be, for example, 0.02 to 2 parts by mass, 0.04 to 1.5 parts by mass, or 0.05 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic polymer. The content of the isocyanate-based crosslinking agent is preferably 0.02 parts by mass or more from the viewpoint of cohesive strength, while it is preferably 2 parts by mass or less from the viewpoint of suppressing or preventing a decrease in adhesive strength due to excessive crosslinking.
[0104] Furthermore, the adhesive may contain, as necessary, tackifiers, plasticizers, fillers made of glass fibers, glass beads, metal powders, other inorganic powders, pigments, colorants, fillers, antioxidants, ultraviolet absorbers, silane coupling agents, etc., and various additives may also be appropriately used within the scope of the object of the present invention. Also, the adhesive layer may contain fine particles and exhibit light diffusing properties.
[0105] [4. Manufacturing method of laminate] The method for producing the laminate of the present invention is not particularly limited, and can be, for example, the production method described below. However, the following description is merely an example and does not limit the present invention in any way. In the following, the void layer, which is a component of the laminate of the present invention, may be referred to as the "void layer of the present invention." Furthermore, the method for producing the void layer of the present invention may be referred to as the "production method of the void layer of the present invention."
[0106] [4-1. Method of manufacturing the void layer] The method for producing a porous layer of the present invention will be described below with reference to examples, although the method for producing a porous layer of the present invention is not limited to the following description.
[0107] The porous layer of the present invention may be formed, for example, by a silicon compound. The porous layer of the present invention may also be formed, for example, by chemical bonding between microporous particles. For example, the microporous particles may be pulverized gel.
[0108] In the method for producing the porous layer of the present invention, for example, the gel crushing step for crushing the gel of the porous body may be performed in one stage, but is preferably performed in multiple crushing stages. The number of crushing stages is not particularly limited, and may be, for example, two stages or three or more stages.
[0109] In the present invention, the shape of the "particles" (e.g., particles of the pulverized gel) is not particularly limited and may be, for example, spherical or non-spherical. In addition, in the present invention, the pulverized particles may be, for example, sol-gel beaded particles, nanoparticles (hollow nanosilica nanoballoon particles), nanofibers, etc.
[0110] In the present invention, for example, the gel is preferably a porous gel, and the pulverized product of the gel is preferably porous, but is not limited thereto.
[0111] In the present invention, the gel pulverized material may be composed of a structure having at least one of the shapes of, for example, a particulate shape, a fibrous shape, and a flat shape. The particulate and flat structural units may be composed of, for example, an inorganic substance. The constituent elements of the particulate structural units may include, for example, at least one element selected from the group consisting of Si, Mg, Al, Ti, Zn, and Zr. The structure (structural unit) forming the particulate shape may be a solid particle or a hollow particle, and specifically, silicone particles, silicone particles having micropores, hollow silica nanoparticles, hollow silica nanoballoons, and the like may be mentioned. The fibrous structural unit is, for example, a nanofiber having a nano-sized diameter, and specifically, cellulose nanofiber, alumina nanofiber, and the like may be mentioned. The flat structural unit may, for example, be a nanoclay, and specifically, nano-sized bentonite (for example, Kunipia F [trade name]) and the like may be mentioned. The fibrous constituent unit is not particularly limited, but may be, for example, at least one fibrous material selected from the group consisting of carbon nanofibers, cellulose nanofibers, alumina nanofibers, chitin nanofibers, chitosan nanofibers, polymer nanofibers, glass nanofibers, and silica nanofibers.
[0112] In the method for producing the void layer of the present invention, the gel crushing step (e.g., the multiple crushing steps, e.g., the first crushing step and the second crushing step) may be performed in, for example, the "other solvent." Details of the "other solvent" will be described later.
[0113] In the present invention, the "solvent" (e.g., a solvent for producing a gel, a solvent for producing a void layer, a replacement solvent, etc.) does not have to dissolve the gel or its pulverized product, etc., and may, for example, disperse or precipitate the gel or its pulverized product, etc. in the solvent.
[0114] The volume average particle diameter of the gel after the first pulverization step may be, for example, 0.5 to 100 μm, 1 to 100 μm, 1 to 50 μm, 2 to 20 μm, or 3 to 10 μm. The volume average particle diameter of the gel after the second pulverization step may be, for example, 10 to 1000 nm, 100 to 500 nm, or 200 to 300 nm. The volume average particle diameter indicates the particle size variation of the pulverized material in the liquid containing the gel (gel-containing liquid). The volume average particle diameter can be measured, for example, by a particle size distribution evaluation device such as a dynamic light scattering method or a laser diffraction method, and an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0115] The method for producing a porous layer of the present invention includes, for example, a gelling step in which a block of porous body is gelled in a solvent to form the gel. In this case, for example, the gel gelled in the gelling step is used in the first crushing step (for example, the first crushing step) of the multiple crushing steps.
[0116] The method for producing the void layer of the present invention includes, for example, an aging step of aging the gel in a solvent. In this case, for example, the gel after the aging step is used in the first crushing step (for example, the first crushing step) of the multiple crushing steps.
[0117] In the method for producing an air gap layer of the present invention, for example, after the gelling step, the solvent replacement step is performed to replace the solvent with another solvent. In this case, for example, the gel in the other solvent is used in the first crushing step (for example, the first crushing step) of the multiple crushing steps.
[0118] In at least one of the multiple grinding stages (e.g., at least one of the first grinding stage and the second grinding stage) of the method for manufacturing a porous layer of the present invention, the grinding of the porous body is controlled, for example, while measuring the shear viscosity of the liquid.
[0119] At least one of the multiple pulverization steps (for example, at least one of the first pulverization step and the second pulverization step) in the method for producing a porous layer of the present invention is carried out by, for example, high-pressure media-less pulverization.
[0120] In the method for producing a porous layer of the present invention, the gel is, for example, a gel of a silicon compound containing at least three or less saturated bond functional groups.
[0121] In the following, in the method for producing a porous layer of the present invention, the gel powder-containing liquid obtained by a process including the gel crushing process may be referred to as "the gel powder-containing liquid of the present invention."
[0122] According to the gel pulverized material-containing liquid of the present invention, for example, a coating film is formed, and the pulverized materials in the coating film are chemically bonded to each other to form the porous layer of the present invention as a functional porous body. According to the gel pulverized material-containing liquid of the present invention, for example, the porous layer of the present invention can be applied to various objects. Therefore, the gel pulverized material-containing liquid of the present invention and its manufacturing method are useful, for example, in the manufacture of the porous layer of the present invention.
[0123] The gel powder-containing liquid of the present invention has, for example, extremely excellent uniformity, and therefore, when the void layer of the present invention is applied to applications such as optical components, the appearance of the component can be improved.
[0124] The gel pulverized material-containing liquid of the present invention may be, for example, a gel pulverized material-containing liquid for obtaining a layer (porous layer) having a high porosity by coating the gel pulverized material-containing liquid on a substrate and drying it. The gel pulverized material-containing liquid of the present invention may also be, for example, a gel pulverized material-containing liquid for obtaining a high porosity porous body (a thick or chunky bulk body). The bulk body can be obtained, for example, by performing bulk film formation using the gel pulverized material-containing liquid.
[0125] For example, the porous layer of the present invention having a high porosity can be produced by a manufacturing method including the steps of producing the gel powder-containing liquid of the present invention, applying the gel powder-containing liquid onto a substrate to form a coating film, and drying the coating film.
[0126] Furthermore, for example, a manufacturing method including the steps of producing the gel powder-containing liquid of the present invention, unwinding the resin film in a roll shape, applying the gel powder-containing liquid to the unwound resin film to form a coating film, drying the coating film, and, after the drying step, winding up the laminate film in which the void layer of the present invention is formed on the resin film, can be used to produce a roll-shaped laminate film (laminate film roll), for example, as shown in Figures 2 and 3 described below.
[0127] [4-2. Liquid containing pulverized gel and its manufacturing method] The gel powder-containing liquid of the present invention contains, for example, the gel powder obtained by the gel crushing step (for example, the first crushing stage and the second crushing stage) and the other solvent.
[0128] The method for producing a void layer of the present invention may include a plurality of gel crushing steps for crushing the gel (e.g., porous gel) as described above, for example, and may include the first crushing step and the second crushing step. Hereinafter, the method for producing a gel crushed material-containing liquid of the present invention will be mainly described by taking as an example a case in which the method includes the first crushing step and the second crushing step. Hereinafter, the method for producing a gel crushed material-containing liquid of the present invention will be mainly described by taking as an example a case in which the gel is a porous body (porous gel). However, the present invention is not limited to this, and the explanation for the case in which the gel is a porous body (porous gel) can be applied by analogy to cases other than the case in which the gel is a porous body. In addition, hereinafter, the plurality of crushing steps (e.g., the first crushing step and the second crushing step) in the method for producing a void layer of the present invention may be collectively referred to as a "gel crushing step".
[0129] The gel pulverized product-containing liquid of the present invention can be used to manufacture a functional porous body that exhibits the same function (e.g., low refractive index) as an air layer, as described below. The functional porous body may be, for example, the void layer of the present invention. Specifically, the gel pulverized product-containing liquid obtained by the manufacturing method of the present invention contains the pulverized product of the porous body gel, and the pulverized product can form a new three-dimensional structure different from the unpulverized porous body gel by destroying the three-dimensional structure of the unpulverized porous body gel. For this reason, for example, a coating film (a precursor of a functional porous body) formed using the gel pulverized product-containing liquid is a layer in which a new pore structure (a new void structure) that cannot be obtained in a layer formed using the unpulverized porous body gel is formed. This allows the layer to exhibit the same function (e.g., similar low refractive index) as an air layer. In addition, the gel pulverized product-containing liquid of the present invention can chemically bond the pulverized products to each other after a new three-dimensional structure is formed as the coating film (a precursor of a functional porous body) by, for example, the pulverized product contains residual silanol groups. As a result, the functional porous body formed has a structure having voids, but can maintain sufficient strength and flexibility. Therefore, according to the present invention, the functional porous body can be easily and simply applied to various objects. The gel pulverized material-containing liquid obtained by the manufacturing method of the present invention is very useful, for example, in the manufacture of the porous structure that can be a substitute for an air layer. In addition, in the case of the air layer, for example, it was necessary to form an air layer between the members by laminating the members with a spacer or the like between them to provide a gap. However, the functional porous body formed using the gel pulverized material-containing liquid of the present invention can exert the same function as the air layer simply by placing it at the desired site. Therefore, as described above, it is easier and simpler to impart the same function as the air layer to various objects than forming the air layer.
[0130] The gel powder-containing liquid of the present invention can be, for example, a solution for forming the functional porous body, or a solution for forming a void layer or a low refractive index layer. In the gel powder-containing liquid of the present invention, the porous body is the pulverized product thereof.
[0131] In the gel pulverized product-containing liquid of the present invention, the volume average particle diameter of the pulverized product (porous gel particles) is, for example, 10 to 1000 nm, 100 to 500 nm, or 200 to 300 nm. The volume average particle diameter indicates the particle size variation of the pulverized product in the gel pulverized product-containing liquid of the present invention. As described above, the volume average particle diameter can be measured by, for example, a particle size distribution evaluation device such as a dynamic light scattering method or a laser diffraction method, or an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0132] In the gel pulverized product-containing liquid of the present invention, the gel concentration of the pulverized product is not particularly limited, and for example, particles having a particle size of 10 to 1000 nm are present at 2.5 to 4.5 wt %, 2.7 to 4.0 wt %, or 2.8 to 3.2 wt %.
[0133] In the gel pulverized product-containing liquid of the present invention, the gel (for example, porous gel) is not particularly limited, and examples thereof include silicon compounds.
[0134] The silicon compound is not particularly limited, and examples thereof include silicon compounds containing at least three or less saturated bond functional groups. The term "containing three or less saturated bond functional groups" means that the silicon compound has three or less functional groups, and these functional groups are saturatedly bonded with silicon (Si).
[0135] The silicon compound is, for example, a compound represented by the following formula (2). [ka]
[0136] In the formula (2), for example, X is 2, 3 or 4, R 1 and R 2 are each a linear or branched alkyl group, R 1 and R 2 may be the same or different, R 1may be the same or different when X is 2, R 2 may be the same or different from each other.
[0137] The X and R 1 For example, X and R in formula (1) described below 1 It is the same as the above. 2 is, for example, R in formula (1) described later. 1 The following example can be used.
[0138] Specific examples of the silicon compound represented by the formula (2) include the compound represented by the following formula (2') in which X is 3. In the following formula (2'), R 1 and R 2 are the same as those in the above formula (2). 1 and R 2 When is a methyl group, the silicon compound is trimethoxy(methyl)silane (hereinafter also referred to as "MTMS"). [ka]
[0139] In the gel pulverized product-containing liquid of the present invention, the solvent may be, for example, a dispersion medium. The dispersion medium (hereinafter also referred to as "coating solvent") is not particularly limited, and may be, for example, a gelling solvent and a grinding solvent described below, and is preferably the grinding solvent. The coating solvent includes an organic solvent having a boiling point of 70°C or more and less than 180°C, and a saturated vapor pressure at 20°C of 15 kPa or less.
[0140] Examples of the organic solvent include carbon tetrachloride, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, trichloroethylene, isobutyl alcohol, isopropyl alcohol, isopentyl alcohol, 1-pentyl alcohol (pentanol), ethyl alcohol (ethanol), ethylene glycol monoethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-butyl ether, ethylene glycol monomethyl ether, xylene, cresol, chlorobenzene, isobutyl acetate, isopropyl acetate, isopentyl acetate, ethyl acetate, n-butyl acetate, n-propyl acetate, n-pentyl acetate, cyclohexanol, cyclohexanone, 1,4-dioxane, N,N-dimethylformamide, styrene, tetrachloroethylene, 1,1,1-trichloroethane, toluene, 1-butanol, 2-butanol, methyl isobutyl ketone, methyl ethyl ketone, methyl cyclohexanol, methyl cyclohexanone, methyl-n-butyl ketone, and isopentanol. The dispersion medium may contain an appropriate amount of a perfluoro-based surfactant, a silicone-based surfactant, or the like, which reduces surface tension.
[0141] The gel pulverized material-containing liquid of the present invention may be, for example, a sol particle liquid in which the pulverized material is in a sol state dispersed in the dispersion medium. The gel pulverized material-containing liquid of the present invention can be, for example, coated on a substrate and dried, and then chemically crosslinked in a bonding step described below, to continuously form a porous layer having a certain level of film strength or higher. Note that the "sol" in the present invention refers to a state in which the pulverized material (i.e., particles of a nano-three-dimensional structured porous sol that retains a part of the void structure) is dispersed in a solvent and exhibits fluidity by pulverizing the three-dimensional structure of the gel.
[0142] The gel powder-containing liquid of the present invention may contain, for example, a catalyst for chemically bonding the gel powders together. The content of the catalyst is not particularly limited, but is, for example, 0.01 to 20% by weight, 0.05 to 10% by weight, or 0.1 to 5% by weight based on the weight of the gel powder.
[0143] The gel powder-containing liquid of the present invention may further contain, for example, a cross-linking auxiliary for indirectly bonding the gel powders together. The content of the cross-linking auxiliary is not particularly limited, but is, for example, 0.01 to 20% by weight, 0.05 to 15% by weight, or 0.1 to 10% by weight based on the weight of the gel powder.
[0144] In addition, in the gel pulverized product-containing liquid of the present invention, the ratio of functional groups that do not contribute to the crosslinked structure in the gel among the functional groups of the constituent unit monomer of the gel may be, for example, 30 mol% or less, 25 mol% or less, 20 mol% or less, 15 mol% or less, and may be, for example, 1 mol% or more, 2 mol% or more, 3 mol% or more, 4 mol% or more. The ratio of functional groups that do not contribute to the crosslinked structure in the gel can be measured, for example, as follows.
[0145] (Method for measuring the proportion of functional groups not contributing to the cross-linked structure in the gel) After drying the gel, solid-state NMR (Si-NMR) is measured, and the ratio of remaining silanol groups that do not contribute to the crosslinked structure (functional groups that do not contribute to the crosslinked structure in the gel) is calculated from the peak ratio of NMR. Even if the functional groups are other than silanol groups, the ratio of functional groups that do not contribute to the crosslinked structure in the gel can be calculated similarly from the peak ratio of NMR.
[0146] The method for producing the gel powder-containing liquid of the present invention will be described below with reference to examples. The following description can be applied to the gel powder-containing liquid of the present invention unless otherwise specified.
[0147] In the method for producing a gel pulverized material-containing liquid of the present invention, the mixing step is a step of mixing the particles (pulverized material) of the porous gel with the solvent, and may or may not be included. A specific example of the mixing step is, for example, a step of mixing a pulverized material of a gel-like silicon compound (silicon compound gel) obtained from a silicon compound containing at least three or less saturated bond functional groups with a dispersion medium. In the present invention, the pulverized material of the porous gel can be obtained from the porous gel by a gel pulverization step described later. In addition, the pulverized material of the porous gel can be obtained, for example, from the porous gel after aging treatment in an aging step described later.
[0148] In the method for producing a gel powder-containing liquid of the present invention, the gelling process is, for example, a process of gelling a block of porous material in a solvent to produce the porous material gel, and a specific example of the gelling process is, for example, a process of gelling a silicon compound containing the at least three or less saturated bond functional groups in a solvent to produce a silicon compound gel.
[0149] The gelling step will be described below by taking as an example a case where the porous body is a silicon compound.
[0150] The gelation step is, for example, a step of gelling the monomeric silicon compound by a dehydration condensation reaction in the presence of a dehydration condensation catalyst, thereby obtaining a silicon compound gel. The silicon compound gel has, for example, residual silanol groups, and the residual silanol groups are preferably appropriately adjusted according to the chemical bonds between the pulverized products of the silicon compound gel described later.
[0151] In the gelation step, the silicon compound is not particularly limited as long as it is gelled by a dehydration condensation reaction. For example, the silicon compounds are bonded to each other by the dehydration condensation reaction. The bond between the silicon compounds is, for example, a hydrogen bond or an intermolecular bond.
[0152] The silicon compound may be, for example, a silicon compound represented by the following formula (1): Since the silicon compound represented by the formula (1) has a hydroxyl group, hydrogen bonds or intermolecular bonds can be formed between the silicon compounds represented by the formula (1) via the respective hydroxyl groups.
[0153] [ka]
[0154] In the formula (1), for example, X is 2, 3 or 4; R 1 is a straight-chain or branched alkyl group. 1 The number of carbon atoms is, for example, 1 to 6, 1 to 4, or 1 to 2. Examples of the linear alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group, and examples of the branched alkyl group include an isopropyl group and an isobutyl group. X is, for example, 3 or 4.
[0155] Specific examples of the silicon compound represented by the formula (1) include the compound represented by the following formula (1') in which X is 3. In the following formula (1'), R 1 is the same as in the formula (1), and is, for example, a methyl group. 1 When X is a methyl group, the silicon compound is tris(hydroxy)methylsilane. When X is 3, the silicon compound is, for example, a trifunctional silane having three functional groups.
[0156] [ka]
[0157] A specific example of the silicon compound represented by the formula (1) is a compound in which X is 4. In this case, the silicon compound is, for example, a tetrafunctional silane having four functional groups.
[0158] The silicon compound may be, for example, a precursor that forms the silicon compound of the formula (1) by hydrolysis. The precursor may be, for example, anything that can generate the silicon compound by hydrolysis, and a specific example of the precursor is the compound represented by the formula (2).
[0159] When the silicon compound is a precursor represented by the formula (2), the production method of the present invention may include, for example, a step of hydrolyzing the precursor prior to the gelation step.
[0160] The hydrolysis method is not particularly limited, and can be carried out, for example, by a chemical reaction in the presence of a catalyst. Examples of the catalyst include acids such as oxalic acid and acetic acid. The hydrolysis reaction can be carried out, for example, by slowly dropping and mixing an aqueous solution of oxalic acid into a dimethylsulfoxide solution of the silicon compound precursor at room temperature, and then stirring the mixture for about 30 minutes. When hydrolyzing the silicon compound precursor, for example, by completely hydrolyzing the alkoxy group of the silicon compound precursor, the subsequent gelation, aging, heating and fixation after the formation of a void structure can be more efficiently achieved.
[0161] In the present invention, the silicon compound may be, for example, a hydrolyzate of trimethoxy(methyl)silane.
[0162] The silicon compound of the monomer is not particularly limited, and can be appropriately selected, for example, according to the application of the functional porous body to be produced. In the production of the functional porous body, for example, when emphasis is placed on low refractive index, the silicon compound is preferably the trifunctional silane from the viewpoint of excellent low refractive index, and when emphasis is placed on strength (for example, scratch resistance), the tetrafunctional silane is preferably from the viewpoint of excellent scratch resistance. In addition, the silicon compound as a raw material of the silicon compound gel may be, for example, only one type, or two or more types may be used in combination. As a specific example, the silicon compound may contain, for example, only the trifunctional silane, only the tetrafunctional silane, or both the trifunctional silane and the tetrafunctional silane, or may further contain other silicon compounds. When two or more types of silicon compounds are used as the silicon compound, the ratio is not particularly limited and can be appropriately set.
[0163] The gelation of the porous body such as the silicon compound can be carried out, for example, by a dehydration condensation reaction between the porous bodies. The dehydration condensation reaction is preferably carried out, for example, in the presence of a catalyst, and examples of the catalyst include acid catalysts such as hydrochloric acid, oxalic acid, and sulfuric acid, and base catalysts such as ammonia, potassium hydroxide, sodium hydroxide, and ammonium hydroxide. The dehydration condensation catalyst may be an acid catalyst or a base catalyst, but a base catalyst is preferred. In the dehydration condensation reaction, the amount of the catalyst added to the porous body is not particularly limited, and the catalyst is, for example, 0.01 to 10 mol, 0.05 to 7 mol, or 0.1 to 5 mol per 1 mol of the porous body.
[0164] The gelation of the porous body such as the silicon compound is preferably carried out in a solvent. The ratio of the porous body in the solvent is not particularly limited. Examples of the solvent include dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc), dimethylformamide (DMF), γ-butyrolactone (GBL), acetonitrile (MeCN), and ethylene glycol ethyl ether (EGEE). The solvent may be one type or two or more types in combination. The solvent used for the gelation is hereinafter also referred to as a "gelation solvent".
[0165] The gelation conditions are not particularly limited. The treatment temperature for the solvent containing the porous body is, for example, 20 to 30°C, 22 to 28°C, or 24 to 26°C, and the treatment time is, for example, 1 to 60 minutes, 5 to 40 minutes, or 10 to 30 minutes. When the dehydration condensation reaction is performed, the treatment conditions are not particularly limited, and these examples can be used. When the porous body is a silicon compound, the gelation causes, for example, siloxane bonds to grow and primary particles of the silicon compound are formed, and the reaction proceeds further, so that the primary particles are linked together in a beaded shape to generate a gel with a three-dimensional structure.
[0166] The gel form of the porous body obtained in the gelling step is not particularly limited. "Gel" generally refers to a state in which solutes have an aggregated structure that has lost independent mobility due to interactions and are solidified. Among gels, wet gel generally refers to a gel containing a dispersion medium and in which the solute has a uniform structure in the dispersion medium, and xerogel refers to a gel in which the solvent has been removed and the solute has a network structure with voids. In the present invention, it is preferable to use, for example, a wet gel as the silicon compound gel. When the porous body gel is a silicon compound gel, the remaining amount of silanol groups in the silicon compound gel is not particularly limited, and can be exemplified by the range described below.
[0167] The porous gel obtained by the gelation may be subjected to the solvent replacement step and the first pulverization step as it is, but may be subjected to an aging treatment in the aging step prior to the first pulverization step. In the aging step, the gelled porous body (porous gel) is aged in a solvent. In the aging step, the conditions of the aging treatment are not particularly limited, and for example, the porous gel may be incubated in a solvent at a predetermined temperature. According to the aging treatment, for example, the primary particles of the porous gel having a three-dimensional structure obtained by gelation can be further grown, and the size of the particles themselves can be increased. As a result, the contact state of the neck part where the particles are in contact with each other can be increased from, for example, point contact to surface contact. The porous gel subjected to the above-mentioned aging treatment has, for example, an increased strength of the gel itself, and as a result, the strength of the three-dimensional basic structure of the pulverized product after pulverization can be further improved. As a result, when a coating film is formed using the gel powder-containing liquid of the present invention, even during the drying process after coating, the pore size of the void structure in which the three-dimensional basic structure is deposited can be prevented from shrinking due to the evaporation of the solvent in the coating film that occurs during the drying process.
[0168] The lower limit of the temperature of the aging treatment is, for example, 30°C or more, 35°C or more, or 40°C or more, and the upper limit is, for example, 80°C or less, 75°C or less, or 70°C or less, and the range is, for example, 30 to 80°C, 35 to 75°C, or 40 to 70°C. The predetermined time is not particularly limited, and the lower limit is, for example, 5 hours or more, 10 hours or more, or 15 hours or more, and the upper limit is, for example, 50 hours or less, 40 hours or less, or 30 hours or less, and the range is, for example, 5 to 50 hours, 10 to 40 hours, or 15 to 30 hours. It is preferable to set the optimal condition of the aging to a condition that, for example, increases the size of the primary particles in the porous gel and increases the contact area of the neck portion, as described above. In addition, in the aging process, it is preferable to consider, for example, the boiling point of the solvent used for the temperature of the aging treatment. In the aging treatment, for example, if the aging temperature is too high, the solvent may volatilize excessively, and the coating liquid may become concentrated, which may cause problems such as closure of pores in the three-dimensional void structure, etc. On the other hand, if the aging temperature is too low, for example, the effect of the aging treatment may not be sufficiently obtained, and temperature variation may increase over time in the mass production process, which may result in a product of inferior quality.
[0169] The aging treatment can use, for example, the same solvent as that used in the gelation step, and is preferably performed directly on the reactant after the gelation treatment (i.e., the solvent containing the porous gel). When the porous gel is the silicon compound gel, the molar number of the residual silanol groups contained in the silicon compound gel after the aging treatment after gelation is, for example, the ratio of the residual silanol groups when the molar number of the alkoxy groups of the raw material (e.g., the silicon compound or its precursor) used for gelation is taken as 100, and the lower limit is, for example, 50% or more, 40% or more, or 30% or more, and the upper limit is, for example, 1% or less, 3% or less, or 5% or less, and the range is, for example, 1 to 50%, 3 to 40%, or 5 to 30%. For the purpose of increasing the hardness of the silicon compound gel, for example, the lower the molar number of the residual silanol groups, the more preferable. If the number of moles of the residual silanol groups is too high, for example, in the formation of the functional porous body, the pore structure may not be maintained until the precursor of the functional porous body is crosslinked. On the other hand, if the number of moles of the residual silanol groups is too low, for example, in the bonding step, the precursor of the functional porous body may not be crosslinked, and sufficient film strength may not be imparted. Note that the above is an example of the residual silanol groups, but for example, when the silicon compound modified with various reactive functional groups is used as the raw material of the silicon compound gel, the same phenomenon can be applied to each functional group.
[0170] The porous gel obtained by the gelation is, for example, subjected to an aging treatment in the aging step, and then subjected to a solvent replacement step, and then subjected to the gel crushing step. In the solvent replacement step, the solvent is replaced with another solvent.
[0171] In the present invention, the gel crushing step is a step of crushing the porous gel as described above. The crushing may be performed, for example, on the porous gel after the gelling step, or on the porous gel after the aging treatment.
[0172] As described above, a gel morphology control step of controlling the shape and size of the gel may be performed prior to the solvent replacement step (e.g., after the aging step). The shape and size of the gel controlled in the gel morphology control step are not particularly limited, but are, for example, as described above. The gel morphology control step may be performed, for example, by dividing (e.g., cutting) the gel into a solid (three-dimensional body) of appropriate size and shape.
[0173] Furthermore, as described above, the gel is subjected to the solvent substitution process before the gel crushing process. In the solvent substitution process, the solvent is replaced with another solvent. If the solvent is not replaced with the other solvent, for example, the catalyst and solvent used in the gelling process remain after the aging process, which may cause further gelling over time and affect the pot life of the gel crushed material-containing liquid obtained at the end, or the drying efficiency may decrease when drying the coating film formed using the gel crushed material-containing liquid. The other solvent in the gel crushing process is also referred to as the "crushing solvent" below.
[0174] The grinding solvent (other solvent) is not particularly limited, and for example, an organic solvent can be used. Examples of the organic solvent include solvents having a boiling point of 140°C or less, 130°C or less, 100°C or less, or 85°C or less. Specific examples include isopropyl alcohol (IPA), ethanol, methanol, n-butanol, 2-butanol, isobutyl alcohol, pentyl alcohol, propylene glycol monomethyl ether (PGME), methyl cellosolve, and acetone. The grinding solvent may be, for example, one type, or two or more types may be used in combination.
[0175] In addition, when the polarity of the grinding solvent is low, for example, the solvent replacement step may be divided into a plurality of solvent replacement stages, and the hydrophilicity of the other solvent may be lower in the later stages than in the earlier stages. In this way, for example, it is possible to improve the solvent replacement efficiency and to extremely reduce the amount of the gel production solvent (e.g., DMSO) remaining in the gel. As a specific example, for example, the solvent replacement step may be divided into three solvent replacement stages, and in the first solvent replacement stage, the DMSO in the gel may be replaced with water, then in the second solvent replacement stage, the water in the gel may be replaced with IPA, and further, in the third replacement stage, the IPA in the gel may be replaced with isobutyl alcohol.
[0176] The combination of the gelling solvent and the grinding solvent is not particularly limited, and examples thereof include a combination of DMSO and IPA, a combination of DMSO and ethanol, a combination of DMSO and isobutyl alcohol, a combination of DMSO and n-butanol, etc. In this way, by replacing the gelling solvent with the grinding solvent, for example, in the coating film formation described later, a more uniform coating film can be formed.
[0177] The solvent replacement step is not particularly limited, but can be carried out, for example, as follows. That is, first, the gel produced by the gel production step (for example, the gel after the aging treatment) is immersed in or contacted with the other solvent, and the catalyst for gel production in the gel, the alcohol component produced by the condensation reaction, water, etc. are dissolved in the other solvent. Thereafter, the solvent in which the gel is immersed or contacted is discarded, and the gel is immersed or contacted again with a new solvent. This is repeated until the remaining amount of the solvent for gel production in the gel reaches a desired amount. The immersion time per one time is, for example, 0.5 hours or more, 1 hour or more, or 1.5 hours or more, and the upper limit is not particularly limited, but is, for example, 10 hours or less. The immersion in the above solvent may be performed by continuously contacting the gel with the solvent. The temperature during the immersion is not particularly limited, but may be, for example, 20 to 70°C, 25 to 65°C, or 30 to 60°C. Although heating can accelerate the solvent replacement and reduce the amount of solvent required for replacement, the solvent replacement may be conveniently performed at room temperature. In addition, for example, when the solvent replacement step is performed in multiple solvent replacement stages, each of the multiple solvent replacement stages may be performed as described above.
[0178] When the solvent replacement step is divided into a plurality of solvent replacement stages and the other solvent is less hydrophilic in the later stages than in the earlier stages, the other solvent (replacement solvent) is not particularly limited. In the last solvent replacement stage, the other solvent (replacement solvent) is preferably a solvent for forming a porous layer. Examples of the solvent for forming a porous layer include solvents having a boiling point of 140° C. or less. Examples of the solvent for forming a porous layer include alcohol, ether, ketone, ester solvents, aliphatic hydrocarbon solvents, aromatic solvents, and the like. Specific examples of alcohols having a boiling point of 140° C. or less include isopropyl alcohol (IPA), ethanol, methanol, n-butanol, 2-butanol, isobutyl alcohol (IBA), 1-pentanol, 2-pentanol, and the like. Specific examples of ethers having a boiling point of 140° C. or less include propylene glycol monomethyl ether (PGME), methyl cellosolve, ethyl cellosolve, and the like. Specific examples of ketones having a boiling point of 140° C. or less include acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone. Specific examples of ester-based solvents having a boiling point of 140° C. or less include ethyl acetate, butyl acetate, isopropyl acetate, and normal propyl acetate. Specific examples of aliphatic hydrocarbon-based solvents having a boiling point of 140° C. or less include hexane, cyclohexane, heptane, and octane. Specific examples of aromatic solvents having a boiling point of 140° C. or less include toluene, benzene, xylene, and anisole. From the viewpoint of not corroding the substrate (e.g., resin film) during coating, the solvent for forming the void layer is preferably an alcohol, ether, or an aliphatic hydrocarbon-based solvent. The pulverizing solvent may be, for example, one type, or two or more types may be used in combination. In particular, isopropyl alcohol (IPA), ethanol, n-butanol, 2-butanol, isobutyl alcohol (IBA), pentyl alcohol, propylene glycol monomethyl ether (PGME), methyl cellosolve, heptane, and octane are preferred in terms of low volatility at room temperature.In particular, in order to suppress scattering of particles (e.g., silica compound) that are the material of the gel, it is preferable that the saturated vapor pressure of the solvent for manufacturing the porous layer is not too high (it is not too volatile). As such a solvent, for example, a solvent having an aliphatic group with 3 or 4 or more carbon atoms is preferable, and a solvent having an aliphatic group with 4 or more carbon atoms is more preferable. The solvent having an aliphatic group with 3 or 4 or more carbon atoms may be, for example, alcohol. Specific examples of such a solvent are preferably isopropyl alcohol (IPA), isobutyl alcohol (IBA), n-butanol, 2-butanol, 1-pentanol, and 2-pentanol, and isobutyl alcohol (IBA) is particularly preferable.
[0179] The other solvent (solvent for replacement) other than the last solvent replacement step is not particularly limited, and examples thereof include alcohol, ether, ketone, etc. Specific examples of alcohol include isopropyl alcohol (IPA), ethanol, methanol, n-butanol, 2-butanol, isobutyl alcohol (IBA), pentyl alcohol, etc. Specific examples of ether include propylene glycol monomethyl ether (PGME), methyl cellosolve, ethyl cellosolve, etc. Specific examples of ketone include acetone, etc. The other solvent (solvent for replacement) may be any solvent that can replace the gel production solvent or the other solvent (solvent for replacement) in the previous step. In addition, the other solvent (solvent for replacement) other than the last solvent replacement step is preferably a solvent that does not ultimately remain in the gel, or, even if it does remain, does not easily corrode the substrate (e.g., a resin film) during coating. From the viewpoint of preventing corrosion of a substrate (e.g., a resin film) during coating, the other solvent (substitution solvent) in the solvent substitution steps other than the last one is preferably alcohol. Thus, in at least one of the multiple solvent substitution steps, the other solvent is preferably alcohol.
[0180] In the initial solvent replacement step, the other solvent may be, for example, water or a mixed solvent containing water at any ratio. Water or a mixed solvent containing water has high compatibility with a highly hydrophilic gel-producing solvent (e.g., DMSO), making it easy to replace the gel-producing solvent and also preferable in terms of cost.
[0181] The multiple solvent replacement steps may include a step in which the other solvent is water, a subsequent step in which the other solvent is a solvent having an aliphatic group with 3 or less carbon atoms, and a subsequent step in which the other solvent is a solvent having an aliphatic group with 4 or more carbon atoms. At least one of the solvent having an aliphatic group with 3 or less carbon atoms and the solvent having an aliphatic group with 4 or more carbon atoms may be an alcohol. The alcohol having an aliphatic group with 3 or less carbon atoms is not particularly limited, but examples thereof include isopropyl alcohol (IPA), ethanol, methanol, and n-propyl alcohol. The alcohol having an aliphatic group with 4 or more carbon atoms is not particularly limited, but examples thereof include n-butanol, 2-butanol, isobutyl alcohol (IBA), and pentyl alcohol. For example, the solvent having an aliphatic group with 3 or less carbon atoms may be isopropyl alcohol, and the solvent having an aliphatic group with 4 or more carbon atoms may be isobutyl alcohol.
[0182] The present inventors have found that it is very important to pay attention to the remaining amount of the gel-producing solvent in order to form a porous layer having sufficient film strength under relatively mild conditions, for example, at 200° C. or less. This finding is not disclosed in the prior art, including the patent documents and non-patent documents, and is a finding that the present inventors have independently found.
[0183] The reason (mechanism) why a low refractive index void layer can be produced by reducing the amount of the gel production solvent remaining in the gel is unclear, but it is speculated as follows. That is, as described above, the gel production solvent is preferably a high boiling point solvent (e.g., DMSO, etc.) for the gelation reaction to proceed. And, when the sol liquid produced from the gel is coated and dried to produce a void layer, it is difficult to completely remove the high boiling point solvent at a normal drying temperature and drying time (not particularly limited, for example, 100°C for 1 minute, etc.). If the drying temperature is too high or the drying time is too long, problems such as deterioration of the substrate may occur. And, it is speculated that the high boiling point solvent remaining during the coating and drying enters between the pulverized pieces of the gel, causing the pulverized pieces to slide against each other, and the pulverized pieces are densely accumulated, reducing the porosity, making it difficult to achieve a low refractive index. That is, conversely, if the amount of the high boiling point solvent remaining is reduced, such a phenomenon can be suppressed and a low refractive index can be achieved. However, these are merely examples of presumed mechanisms and do not limit the present invention in any way.
[0184] In the present invention, the "solvent" (e.g., a solvent for producing a gel, a solvent for producing a void layer, a replacement solvent, etc.) does not have to dissolve the gel or its pulverized product, etc., and may, for example, disperse or precipitate the gel or its pulverized product, etc. in the solvent.
[0185] As described above, the gel-producing solvent may have a boiling point of, for example, 140° C. or higher.
[0186] The solvent for producing the gel is, for example, a water-soluble solvent. In the present invention, the term "water-soluble solvent" refers to a solvent that can be mixed with water in any ratio.
[0187] When the solvent replacement step is divided into a plurality of solvent replacement stages, the method is not particularly limited, but each solvent replacement stage can be performed, for example, as follows. That is, first, the gel is immersed in or contacted with the other solvent, and the catalyst for gel production in the gel, the alcohol component produced by the condensation reaction, water, etc. are dissolved in the other solvent. Thereafter, the solvent in which the gel is immersed or contacted is discarded, and the gel is immersed or contacted again with a new solvent. This is repeated until the remaining amount of the solvent for gel production in the gel reaches a desired amount. The immersion time per one time is, for example, 0.5 hours or more, 1 hour or more, or 1.5 hours or more, and the upper limit is not particularly limited, but is, for example, 10 hours or less. The immersion of the above solvent may be performed by continuous contact of the gel with the solvent. The temperature during the immersion is not particularly limited, but may be, for example, 20 to 70°C, 25 to 65°C, or 30 to 60°C. When heating is performed, the solvent replacement proceeds quickly and the amount of solvent required for replacement is small, but the solvent replacement may be performed simply at room temperature. In this solvent replacement stage, the other solvent (replacement solvent) is gradually changed from a highly hydrophilic solvent to a less hydrophilic (highly hydrophobic) solvent, and the replacement is performed multiple times. In order to remove a highly hydrophilic gel production solvent (e.g., DMSO, etc.), for example, as described above, it is simple and efficient to first use water as a replacement solvent. Then, after removing DMSO, etc. with water, the water in the gel is replaced, for example, with isopropyl alcohol ⇒ isobutyl alcohol (coating solvent) in that order. That is, since water and isobutyl alcohol have low compatibility, the solvent replacement can be performed efficiently by replacing it with isopropyl alcohol once and then with isobutyl alcohol, which is a coating solvent. However, this is just one example, and as described above, the other solvent (replacement solvent) is not particularly limited.
[0188] In the present invention, the method for producing a gel may be carried out several times by gradually changing the other solvent (solvent for replacement) from a solvent with high hydrophilicity to a solvent with low hydrophilicity (high hydrophobicity) in the solvent replacement step, as described above. This makes it possible to reduce the amount of the solvent for producing the gel remaining in the gel, as described above. In addition, it is possible to reduce the amount of solvent used to a much smaller amount, and to reduce costs, compared to a case where solvent replacement is carried out in one step using only a solvent for coating, for example.
[0189] Then, after the solvent replacement step, a gel crushing step is performed in which the gel is crushed in the crushing solvent. Also, for example, as described above, after the solvent replacement step, a gel concentration measurement may be performed before the gel crushing step, if necessary, and further, the gel concentration adjustment step may be performed thereafter, if necessary. The gel concentration measurement after the solvent replacement step and before the gel crushing step can be performed, for example, as follows. That is, first, after the solvent replacement step, the gel is taken out from the other solvent (crushing solvent). This gel is controlled, for example, by the gel morphology control step, into a lump of an appropriate shape and size (for example, a block shape). Next, after removing the solvent adhering to the periphery of the gel lump, the solid content concentration in one gel lump is measured by a weight drying method. At this time, in order to obtain reproducibility of the measured value, the measurement is performed on multiple (for example, six) lumps taken out randomly, and the average value and the variation of the value are calculated. The concentration adjustment step may further include adding the other solvent (grinding solvent) to decrease the gel concentration of the gel-containing liquid, or may conversely include evaporating the other solvent (grinding solvent) to increase the gel concentration of the gel-containing liquid.
[0190] In the method for producing a gel powder-containing liquid of the present invention, as described above, the gel crushing step may be performed in one step, but it is preferable to perform the gel crushing step in multiple crushing steps. Specifically, for example, the first crushing step and the second crushing step may be performed. In addition to the first crushing step and the second crushing step, the gel crushing step may further include a gel crushing step. That is, in the production method of the present invention, the gel crushing step is not limited to only two crushing steps, but may include three or more crushing steps.
[0191] In this manner, a liquid (e.g., a suspension) containing the microporous particles (pulverized gel-like compound) can be prepared. Furthermore, after preparing the liquid containing the microporous particles, or during the preparation process, a catalyst that chemically bonds the microporous particles to each other can be added to prepare a liquid containing the microporous particles and the catalyst. The amount of the catalyst added is not particularly limited, but is, for example, 0.01 to 20% by weight, 0.05 to 10% by weight, or 0.1 to 5% by weight based on the weight of the pulverized gel-like silicon compound. The catalyst may be, for example, a catalyst that promotes cross-linking between the microporous particles. As a chemical reaction that chemically bonds the microporous particles to each other, it is preferable to utilize a dehydration condensation reaction of residual silanol groups contained in silica sol molecules. By promoting the reaction between hydroxyl groups of silanol groups with the catalyst, continuous film formation that hardens the void structure in a short time is possible. Examples of the catalyst include a photoactive catalyst and a thermally active catalyst. According to the photoactive catalyst, for example, in the void layer forming process, the microporous particles can be chemically bonded (for example, cross-linked) to each other without heating. According to this, for example, in the void layer forming process, the entire void layer is unlikely to shrink, so that a higher porosity can be maintained. In addition to or instead of the catalyst, a substance that generates a catalyst (catalyst generator) may be used. For example, in addition to or instead of the photoactive catalyst, a substance that generates a catalyst by light (photocatalyst generator) may be used, and in addition to or instead of the thermally active catalyst, a substance that generates a catalyst by heat (thermal catalyst generator) may be used. The photocatalyst generator is not particularly limited, but examples thereof include a photobase generator (a substance that generates a basic catalyst by light irradiation), a photoacid generator (a substance that generates an acidic catalyst by light irradiation), and the like, and a photobase generator is preferable.Examples of the photobase generator include 9-anthrylmethyl N,N-diethylcarbamate (trade name WPBG-018), (E)-1-[3-(2-hydroxyphenyl)-2-propenoyl]piperidine (trade name WPBG-027), 1-(anthraquinon-2-yl)ethyl imidazolecarboxylate (trade name WPBG-140), 2-nitrophenylmethyl 4-methacryloyloxypiperidine-1-carboxylate (trade name WPBG-165), and 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidium. Examples of the photoacid generator include 2-(3-benzoylphenyl)propionate (trade name WPBG-266), 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidium n-butyltriphenylborate (trade name WPBG-300), and 2-(9-oxoxanthen-2-yl)propionic acid 1,5,7-triazabicyclo[4.4.0]dec-5-ene (Tokyo Chemical Industry Co., Ltd.), a compound containing 4-piperidinemethanol (trade name HDPD-PB100: manufactured by Heraeus). The trade names containing "WPBG" are all trade names of Wako Pure Chemical Industries, Ltd. Examples of the photoacid generator include aromatic sulfonium salts (trade name SP-170: manufactured by ADEKA), triarylsulfonium salts (trade name CPI101A: manufactured by San-Apro), and aromatic iodonium salts (trade name Irgacure250: manufactured by Ciba Japan). The catalyst for chemically bonding the microporous particles is not limited to the photoactive catalyst and the photocatalyst generator, and may be, for example, a thermally active catalyst or a thermal catalyst generator. Examples of the catalyst for chemically bonding the microporous particles include base catalysts such as potassium hydroxide, sodium hydroxide, and ammonium hydroxide, and acid catalysts such as hydrochloric acid, acetic acid, and oxalic acid. Among these, base catalysts are preferred.The catalyst or catalyst generator that chemically bonds the microporous particles together can be used, for example, by adding it to a sol particle liquid (e.g., a suspension) containing the pulverized material (microporous particles) just before coating, or can be used as a mixed liquid in which the catalyst or catalyst generator is mixed with a solvent. The mixed liquid can be, for example, a coating liquid directly added to the sol particle liquid to dissolve it, a solution in which the catalyst or catalyst generator is dissolved in a solvent, or a dispersion in which the catalyst or catalyst generator is dispersed in a solvent. The solvent is not particularly limited, and examples thereof include water, a buffer solution, and the like.
[0192] In addition, for example, after preparing the liquid containing the microporous particles, a small amount of a high-boiling point solvent can be added to the microporous particle-containing liquid to improve the appearance of the film when the film is formed by coating. The amount of the high-boiling point solvent is not particularly limited, but is, for example, 0.05 to 0.8 times, 0.1 to 0.5 times, and particularly 0.15 to 0.4 times the amount of the solid content of the microporous particle-containing liquid. The high-boiling point solvent is not particularly limited, but examples thereof include dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), γ-butyrolactone (GBL), and ethylene glycol ethyl ether (EGEE). Solvents with a boiling point of 110° C. or more are particularly preferred, and are not limited to the specific examples. It is considered that the high-boiling point solvent acts as a leveling agent when forming a film in which particles are arranged side by side. It is also preferable to use the high-boiling point solvent during gel synthesis. However, it is more effective to completely remove the solvent used in synthesis, and then add the high boiling point solvent after preparing the liquid containing the microporous particles, although the details are unclear. In addition, the added high boiling point solvent remains in the membrane skeleton even after the membrane is formed, and is considered to affect the penetration of the adhesive directly laminated to the membrane into the voids in the membrane. In other words, it is speculated that a slight difference in the solvent solubility of the adhesive to the high boiling point solvent in the membrane is one of the factors that causes the difference in the penetration of the adhesive into the voids in the membrane. However, these mechanisms are merely examples and do not limit the present invention in any way.
[0193] [4-3. Manufacturing methods of laminate, void layer, and adhesive layer] The manufacturing method of the laminate of the present invention will be described below with examples, together with the manufacturing method of the void layer and the manufacturing method of the adhesive layer that constitute the laminate.The following mainly describes the case where the void layer of the present invention is a silicone porous body formed by a silicon compound.However, the void layer of the present invention is not limited to only a silicone porous body.When the void layer of the present invention is other than a silicone porous body, the following description can be applied mutatis mutandis unless otherwise specified.
[0194] The method for producing the void layer of the present invention includes, for example, a precursor formation step of forming a precursor of the void layer using the gel powder-containing liquid of the present invention, and a bonding step of chemically bonding the pulverized substances of the gel powder-containing liquid contained in the precursor. The precursor can also be called, for example, a coating film.
[0195] According to the method for producing the void layer of the present invention, for example, a porous structure that has the same function as an air layer is formed. The reason is presumed to be as follows, but the present invention is not limited to this presumption. Hereinafter, the case where the void layer of the present invention is a silicone porous body will be described as an example.
[0196] The gel pulverized material-containing liquid of the present invention used in the method for producing a silicone porous body contains the pulverized material of the silicon compound gel, so that the three-dimensional structure of the gel-like silica compound is dispersed in the three-dimensional basic structure. Therefore, in the method for producing a silicone porous body, for example, when the precursor (for example, a coating film) is formed using the gel pulverized material-containing liquid, the three-dimensional basic structure is deposited, and a void structure based on the three-dimensional basic structure is formed. In other words, according to the method for producing a silicone porous body, a new three-dimensional structure is formed from the pulverized material of the three-dimensional basic structure, which is different from the three-dimensional structure of the silicon compound gel. In addition, in the method for producing a silicone porous body, the pulverized material is further chemically bonded to each other, so that the new three-dimensional structure is fixed. Therefore, the silicone porous body obtained by the method for producing a silicone porous body has a void structure, but can maintain sufficient strength and flexibility. The porous layer (e.g., a silicone porous body) obtained by the present invention can be used, for example, as a component that utilizes voids in products in a wide range of fields, such as heat insulating materials, sound absorbing materials, optical components, and ink receiving layers, and can also be used to produce laminated films with various functions.
[0197] Unless otherwise specified, the manufacturing method of the porous layer of the present invention can be based on the explanation of the gel powder-containing liquid of the present invention described above.
[0198] In the step of forming the precursor of the porous body, for example, the gel pulverized material-containing liquid of the present invention is applied onto the substrate. After the gel pulverized material-containing liquid of the present invention is applied onto the substrate and the coating film is dried, the pulverized materials are chemically bonded (for example, cross-linked) to each other in the bonding step, so that a porous layer having a certain level or more of film strength can be continuously formed.
[0199] The amount of the gel powder-containing liquid to be applied to the substrate is not particularly limited and can be appropriately set depending on, for example, the desired thickness of the porous layer of the present invention. As a specific example, when forming a silicone porous body having a thickness of 0.1 to 1000 μm, the amount of the gel powder-containing liquid to be applied to the substrate is set to 1 m2 of the area of the substrate.2 For example, the amount of the pulverized material is 0.01 to 60,000 μg, 0.1 to 5,000 μg, or 1 to 50 μg per coating. The preferred amount of coating of the gel pulverized material-containing liquid is difficult to define uniquely because it is related to, for example, the concentration of the liquid and the coating method, but in consideration of productivity, it is preferable to coat it in as thin a layer as possible. If the amount of coating is too large, for example, the solvent is likely to be dried in a drying oven before it evaporates. As a result, the nano-pulverized sol particles settle and accumulate in the solvent, and before the void structure is formed, the solvent dries, which may inhibit the formation of voids and greatly reduce the porosity. On the other hand, if the amount of coating is too thin, there is a high risk of coating repelling due to unevenness and variations in hydrophilicity and hydrophobicity of the substrate.
[0200] After the gel pulverized liquid is applied to the substrate, the porous body precursor (coating film) may be subjected to a drying treatment. The drying treatment is intended not only to remove the solvent (solvent contained in the gel pulverized liquid) in the porous body precursor, but also to cause the sol particles to settle and deposit during the drying treatment to form a void structure. The temperature of the drying treatment is, for example, 50 to 250°C, 60 to 150°C, or 70 to 130°C, and the drying treatment time is, for example, 0.1 to 30 minutes, 0.2 to 10 minutes, or 0.3 to 3 minutes. The drying treatment temperature and time are preferably lower and shorter in terms of, for example, continuous productivity and the development of a high porosity. If the conditions are too severe, for example, in the case where the substrate is a resin film, the substrate may expand in a drying oven as the substrate approaches the glass transition temperature of the substrate, and defects such as cracks may occur in the formed void structure immediately after coating. On the other hand, if the conditions are too lenient, for example, the film will contain residual solvent when it leaves the drying oven, which may result in appearance defects such as scratches when rubbed against a roll in the next process.
[0201] The drying process may be, for example, natural drying, heat drying, or reduced pressure drying. The drying method is not particularly limited, and for example, a general heating means can be used. Examples of the heating means include a hot air blower, a heating roll, and a far-infrared heater. Among them, when it is assumed that the product will be continuously produced industrially, it is preferable to use heat drying. In addition, the solvent used is preferably a solvent with low surface tension in order to suppress the generation of shrinkage stress caused by the solvent volatilization during drying and the crack phenomenon of the void layer (the silicone porous body) due to the shrinkage stress. Examples of the solvent include, but are not limited to, lower alcohols such as isopropyl alcohol (IPA), hexane, and perfluorohexane.
[0202] The substrate is not particularly limited, and for example, a substrate made of a thermoplastic resin, a substrate made of glass, an inorganic substrate such as silicon, a plastic molded from a thermosetting resin, an element such as a semiconductor, a carbon fiber material such as a carbon nanotube, etc. can be preferably used, but is not limited thereto. The form of the substrate can be, for example, a film, a plate, etc. Examples of the thermoplastic resin include polyethylene terephthalate (PET), acrylic, cellulose acetate propionate (CAP), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), etc.
[0203] In the method for producing a porous layer of the present invention, the bonding step is a step of chemically bonding the pulverized materials contained in the precursor (coating film) of the porous body. The bonding step fixes, for example, the three-dimensional structure of the pulverized materials in the precursor of the porous body. When fixing by conventional sintering, for example, a high-temperature treatment at 200°C or higher is performed to induce a dehydration condensation reaction of silanol groups and the formation of siloxane bonds. In the bonding step of the present invention, by reacting various additives that catalyze the above-mentioned dehydration condensation reaction, for example, when the substrate is a resin film, a void structure can be continuously formed and fixed at a relatively low drying temperature of around 100°C and in a short treatment time of less than a few minutes without causing damage to the substrate.
[0204] The method of chemically bonding is not particularly limited, and can be appropriately determined depending on the type of the gel (e.g., silicon compound gel). As a specific example, the chemical bonding can be performed by chemical cross-linking between the pulverized materials. In addition, when inorganic particles such as titanium oxide are added to the pulverized material, the inorganic particles and the pulverized material can be chemically cross-linked. In addition, when a biocatalyst such as an enzyme is supported, a site other than the catalytic active site and the pulverized material can be chemically cross-linked. Therefore, the present invention can be applied to, for example, not only the void layer formed between the sol particles, but also organic-inorganic hybrid void layers, host-guest void layers, etc., but is not limited thereto.
[0205] The bonding step can be carried out by a chemical reaction in the presence of a catalyst depending on the type of the pulverized gel (e.g., silicon compound gel). As the chemical reaction in the present invention, it is preferable to utilize a dehydration condensation reaction of the residual silanol groups contained in the pulverized silicon compound gel. By promoting the reaction between the hydroxyl groups of the silanol groups with the catalyst, continuous film formation in which the void structure is hardened in a short time is possible. Examples of the catalyst include, but are not limited to, base catalysts such as potassium hydroxide, sodium hydroxide, and ammonium hydroxide, and acid catalysts such as hydrochloric acid, acetic acid, and oxalic acid. The catalyst for the dehydration condensation reaction is particularly preferably a base catalyst. In addition, photoacid generating catalysts and photobase generating catalysts, which exhibit catalytic activity upon irradiation with light (e.g., ultraviolet light), can also be preferably used. The photoacid generating catalyst and photobase generating catalyst are not particularly limited, but are, for example, as described above. For example, as described above, the catalyst is preferably used by adding it to the sol particle liquid containing the pulverized material immediately before coating, or used as a mixed liquid in which the catalyst is mixed with a solvent. The mixed liquid may be, for example, a coating liquid obtained by directly adding the sol particle liquid to dissolve the catalyst, a solution obtained by dissolving the catalyst in a solvent, or a dispersion obtained by dispersing the catalyst in a solvent. The solvent is not particularly limited, and examples of the solvent include water and a buffer solution, as described above.
[0206] In addition, for example, a crosslinking auxiliary for indirectly bonding the pulverized gel materials together may be added to the gel-containing liquid of the present invention. This crosslinking auxiliary penetrates between the particles (the pulverized materials) and the particles and the crosslinking auxiliary interact or bond with each other, making it possible to bond even particles that are somewhat distant from each other, and it is possible to efficiently increase strength. As the crosslinking auxiliary, a multi-crosslinking silane monomer is preferable. Specifically, the multi-crosslinking silane monomer may have, for example, 2 to 3 alkoxysilyl groups, and the chain length between the alkoxysilyl groups may be 1 to 10 carbon atoms, and may also contain elements other than carbon. Examples of the crosslinking auxiliary include bis(trimethoxysilyl)ethane, bis(triethoxysilyl)ethane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triethoxysilyl)propane, bis(trimethoxysilyl)propane, bis(triethoxysilyl)butane, bis(trimethoxysilyl)butane, bis(triethoxysilyl)pentane, bis(trimethoxysilyl)pentane, bis(triethoxysilyl)hexane, bis(trimethoxysilyl)hexane, bis(trimethoxysilyl)-N-butyl-N-propyl-ethane-1,2-diamine, tris-(3-trimethoxysilylpropyl)isocyanurate, and tris-(3-triethoxysilylpropyl)isocyanurate. The amount of the crosslinking auxiliary added is not particularly limited, but is, for example, 0.01 to 20% by weight, 0.05 to 15% by weight, or 0.1 to 10% by weight relative to the weight of the pulverized silicon compound.
[0207] The chemical reaction in the presence of the catalyst can be carried out, for example, by irradiating or heating the coating film containing the catalyst or catalyst generator previously added to the gel pulverized material-containing liquid, spraying the catalyst onto the coating film and then irradiating or heating the coating film, or irradiating or heating the coating film while spraying the catalyst or catalyst generator. For example, when the catalyst is a photoactive catalyst, the microporous particles can be chemically bonded together by light irradiation to form the silicone porous body. When the catalyst is a thermally active catalyst, the microporous particles can be chemically bonded together by heating to form the silicone porous body. The amount of light irradiation (energy) in the light irradiation is not particularly limited, but is, for example, 200 to 800 mJ / cm in terms of @360 nm. 2 , 250~600mJ / cm 2 , or 300-400mJ / cm 2 From the viewpoint of preventing insufficient effect due to insufficient irradiation amount resulting in insufficient decomposition of the catalyst generator by light absorption, it is set to 200 mJ / cm 2 In addition, from the viewpoint of preventing damage to the substrate under the air gap layer and the occurrence of thermal wrinkles, an integrated light quantity of 800 mJ / cm or more is preferable. 2 The following integrated light amount is preferable. The wavelength of the light in the light irradiation is not particularly limited, but is, for example, 200 to 500 nm, 300 to 450 nm. The light irradiation time in the light irradiation is not particularly limited, but is, for example, 0.1 to 30 minutes, 0.2 to 10 minutes, or 0.3 to 3 minutes. The conditions of the heat treatment are not particularly limited, and the heating temperature is, for example, 50 to 250°C, 60 to 150°C, or 70 to 130°C, and the heating time is, for example, 0.1 to 30 minutes, 0.2 to 10 minutes, or 0.3 to 3 minutes. In addition, the solvent used is preferably a solvent with low surface tension, for example, for the purpose of suppressing the generation of shrinkage stress accompanying solvent volatilization during drying and the resulting crack phenomenon of the void layer. Examples of the solvent include, but are not limited to, lower alcohols such as isopropyl alcohol (IPA), hexane, and perfluorohexane.
[0208] In the manner described above, the porous layer of the present invention (for example, a silicone porous body) can be produced. However, the method for producing the porous layer of the present invention is not limited to the above. Hereinafter, the porous layer of the present invention, which is a silicone porous body, may be referred to as the "silicone porous body of the present invention."
[0209] In the production of the laminate of the present invention, a tacky adhesive layer is further formed on the void layer of the present invention (tacky adhesive layer forming step). Specifically, for example, the tacky adhesive layer may be formed by applying (coating) a pressure-sensitive adhesive or adhesive on the void layer of the present invention. The tacky adhesive layer may also be formed on the void layer of the present invention by bonding the tacky adhesive layer side of an adhesive tape or the like in which the tacky adhesive layer is laminated on a substrate to the void layer of the present invention. In this case, the substrate such as the adhesive tape may be left as it is or may be peeled off from the tacky adhesive layer. In particular, as described above, by peeling off the substrate to form a void layer-containing tacky adhesive sheet that does not have a substrate (substrate-less), the thickness can be significantly reduced and an increase in the thickness of a device or the like can be suppressed. In the present invention, the "tacky adhesive" and the "tacky adhesive layer" refer to, for example, an agent or layer that is premised on re-peeling of the adherend. In the present invention, the "adhesive" and the "adhesive layer" refer to, for example, an agent or layer that is not premised on re-peeling of the adherend. However, in the present invention, the "adhesive" and the "adhesive" are not necessarily clearly distinguishable, and the "adhesive layer" and the "adhesive layer" are not necessarily clearly distinguishable. In the present invention, the adhesive or adhesive forming the adhesive layer is not particularly limited, and for example, a general adhesive or adhesive can be used. Examples of the adhesive or adhesive include polymer adhesives such as acrylic, vinyl alcohol, silicone, polyester, polyurethane, and polyether adhesives, and rubber adhesives. In addition, examples of the adhesive include adhesives composed of water-soluble crosslinking agents of vinyl alcohol polymers such as glutaraldehyde, melamine, and oxalic acid. Examples of the adhesive include the adhesives described above. These adhesives and adhesives may be used alone or in combination (for example, mixed, laminated, etc.). As described above, the adhesive layer can protect the void layer from physical damage (especially scratches). The adhesive layer is preferably excellent in pressure resistance so that the void layer is not crushed even in a void layer-containing adhesive sheet that does not have a substrate (substrate-less), but is not particularly limited. The thickness of the adhesive layer is not particularly limited, but is, for example, 0.1 to 100 μm, 5 to 50 μm, 10 to 30 μm, or 12 to 25 μm.
[0210] The porous layer of the present invention thus obtained may be, for example, further laminated with another film (layer) to form a laminated structure containing the porous structure. In this case, in the laminated structure, each component may be laminated, for example, via the adhesive layer (adhesive or adhesive).
[0211] The lamination of each of the components may be performed, for example, by continuous processing (so-called roll to roll, etc.) using a long film, since this is efficient. When the substrate is a molded product, element, etc., the components may be laminated after batch processing.
[0212] The method of forming the laminate of the present invention on a substrate (resin film) will be described below with reference to Figs. 1 to 3, which are examples of continuous processing steps. Fig. 2 shows a process of laminating a protective film after forming the void layer (silicone porous body) and winding it up, but when laminating to another functional film, the above method may be used, or after coating and drying another functional film, the void layer on which the above film formation has been performed may be laminated just before winding up. Note that the film formation methods shown in the figures are merely examples, and are not limited thereto.
[0213] The substrate may be the resin film described above. In this case, the void layer of the present invention is obtained by forming the void layer on the substrate. The void layer of the present invention can also be obtained by forming the void layer on the substrate, and then laminating the void layer on the resin film described above in the description of the void layer of the present invention.
[0214] The cross-sectional view of Fig. 1 shows a schematic example of a process in the method for producing the laminate of the present invention in which the void layer, the intermediate layer and the adhesive layer are laminated in the above order on the substrate (resin film). In Fig. 1, the method for forming the void layer includes a coating step (1) of coating a sol particle liquid 20'' of the pulverized product of the gel-like compound on the substrate (resin film) 10 to form a coating film, a drying step (2) of drying the sol particle liquid 20'' to form a coating film 20' after drying, a chemical treatment step (e.g., a crosslinking step) (3) of chemically treating (e.g., crosslinking) the coating film 20' to form the void layer 20, a viscous adhesive layer coating step (adhesive layer forming step) (4) of coating the viscous adhesive layer 30 on the void layer 20, and an intermediate layer forming step (5) of reacting the void layer 20 with the viscous adhesive layer 30 to form the intermediate layer 22. The chemical treatment step (crosslinking step) (3) corresponds to the "void layer forming step" in the laminated film manufacturing method of the present invention. In addition, in the figure, the intermediate layer forming step (5) (hereinafter sometimes referred to as "aging step") also serves as a step of improving the strength of the void layer 20 (a crosslinking reaction step of causing a crosslinking reaction inside the void layer 20), and after the intermediate layer forming step (5), the void layer 20 is changed into the void layer 21 with improved strength. However, the present invention is not limited to this, and for example, the void layer 20 may not be changed after the intermediate layer forming step (5). In addition, as described above, the adhesive layer forming step is not limited to coating of an adhesive layer, and may be bonding of an adhesive tape having an adhesive layer, etc. By the above steps (1) to (5), a laminated film can be manufactured in which the void layer 21, the intermediate layer 22, and the adhesive layer 30 are laminated in the above order on the resin film 10 as shown in the figure. However, the intermediate layer forming step (5) may be omitted, and the laminate produced according to the present invention may not include an intermediate layer. Furthermore, the method for producing the laminate film according to the present invention may or may not include steps other than the steps (1) to (5) as appropriate.
[0215] In the coating step (1), the coating method of the sol particle liquid 20'' is not particularly limited, and a general coating method can be adopted. Examples of the coating method include a slot die method, a reverse gravure coating method, a microgravure method (microgravure coating method), a dip method (dip coating method), a spin coating method, a brush coating method, a roll coating method, a flexographic printing method, a wire bar coating method, a spray coating method, an extrusion coating method, a curtain coating method, and a reverse coating method. Among these, from the viewpoints of productivity, smoothness of the coating film, and the like, the extrusion coating method, the curtain coating method, the roll coating method, and the microgravure coating method are preferred. The coating amount of the sol particle liquid 20'' is not particularly limited, and can be appropriately set, for example, so that the thickness of the void layer 20 is appropriate. The thickness of the void layer 21 is not particularly limited, and is, for example, as described above.
[0216] In the drying step (2), the sol particle liquid 20'' is dried (i.e., the dispersion medium contained in the sol particle liquid 20'' is removed) to form a dried coating film (precursor of the porous layer) 20'. The conditions for the drying process are not particularly limited and are as described above.
[0217] Furthermore, in the chemical treatment step (3), the coating film 20' containing the catalyst or catalyst generator (e.g., a photoactive catalyst, a photocatalyst generator, a thermally active catalyst, or a thermal catalyst generator) added before coating is irradiated with light or heated to chemically bond (e.g., crosslink) the pulverized materials in the coating film 20' to each other to form the void layer 20. The light irradiation or heating conditions in the chemical treatment step (3) are not particularly limited and are as described above.
[0218] Further, a tacky adhesive layer coating step (tacky adhesive layer forming step) (4) and an intermediate layer forming step (5) are performed. The tacky adhesive layer coating step (tacky adhesive layer forming step) (4) may include, for example, a heating step of heating the tacky adhesive after coating in addition to the step of coating the tacky adhesive. For example, when the tacky adhesive is a tacky adhesive composition containing a polymer (e.g., a (meth)acrylic polymer) and a crosslinking agent, the polymer may be crosslinked by the crosslinking agent by the heating step. The heating step may also serve as, for example, a step of drying the tacky adhesive. Also, for example, the heating step may also serve as the intermediate layer forming step (5). The temperature of the heating step is not particularly limited, but is, for example, 70 to 160°C, 80 to 155°C, or 90 to 150°C. The time of the heating step is not particularly limited, but is, for example, 1 to 10 minutes, 1 to 7 minutes, or 2 to 5 minutes.
[0219] Next, an example of a coating device for the slot die method and a method for forming the void layer using the same are shown in Fig. 2. Although Fig. 2 is a cross-sectional view, hatching has been omitted for ease of viewing.
[0220] As shown in the figure, each step in the method using this apparatus is performed while transporting the substrate 10 in one direction by rollers. The transport speed is not particularly limited and is, for example, 1 to 100 m / min, 3 to 50 m / min, or 5 to 30 m / min.
[0221] First, while the substrate 10 is being fed from the delivery roller 101 and transported, a coating step (1) is performed in which the substrate 10 is coated with a sol particle liquid 20'' by a coating roll 102, and then the process moves to a drying step (2) in an oven zone 110. In the coating device of FIG. 2, after the coating step (1), a pre-drying step is performed prior to the drying step (2). The pre-drying step can be performed at room temperature without heating. In the drying step (2), a heating means 111 is used. As described above, a hot air blower, a heating roll, a far-infrared heater, or the like can be appropriately used as the heating means 111. Also, for example, the drying step (2) may be divided into a plurality of steps, and the drying temperature may be increased in the later drying steps.
[0222] After the drying step (2), the chemical treatment step (3) is carried out in the chemical treatment zone 120. In the chemical treatment step (3), for example, when the dried coating film 20' contains a photoactive catalyst, light is irradiated by lamps (light irradiation means) 121 arranged above and below the substrate 10. Alternatively, for example, when the dried coating film 20' contains a thermally active catalyst, hot air blowers (heating means) are used instead of the lamps (light irradiation devices) 121, and the substrate 10 is heated by the hot air blowers 121 arranged above and below the substrate 10. This crosslinking treatment causes chemical bonding between the pulverized materials in the coating film 20', and the void layer 20 is hardened and strengthened. In this example, the chemical treatment step (3) is carried out after the drying step (2), but as described above, there is no particular limit to the stage at which the pulverized materials are chemically bonded to each other in the manufacturing method of the present invention. For example, as described above, the drying step (2) may also serve as the chemical treatment step (3). Even if the chemical bonds occur in the drying step (2), the chemical bonds between the pulverized materials may be further strengthened by performing a chemical treatment step (3).The chemical bonds between the pulverized materials may also occur in a step prior to the drying step (2) (e.g., a pre-drying step, a coating step (1), a step of preparing a coating liquid (e.g., a suspension), etc.).
[0223] After the chemical treatment step (3), a tacky adhesive layer coating step (tacky adhesive layer forming step) (4) is performed in which a tacky adhesive layer coating means 131a coats (coats) a tacky adhesive or adhesive on the porous layer 20 in the tacky adhesive layer coating zone 130a to form a tacky adhesive layer 30. Also, as described above, instead of coating (coating) the tacky adhesive or adhesive, a tacky adhesive tape or the like having the tacky adhesive layer 30 may be attached (attached).
[0224] Furthermore, an intermediate layer forming step (aging step) (5) is performed in the intermediate layer forming zone (aging zone) 130, and the void layer 20 and the adhesive layer 30 are reacted to form the intermediate layer 22. As described above, in this step, a crosslinking reaction occurs inside the void layer 20, and the void layer 21 has improved strength. The intermediate layer forming step (aging step) (5) may be performed, for example, by heating the void layer 20 and the adhesive layer 30 using hot air blowers (heating means) 131 arranged above and below the substrate 10. The heating temperature, time, etc. are not particularly limited, but are, for example, as described above.
[0225] Then, after the intermediate formation step (aging step) (5), the laminate in which the void layer 21 is formed on the substrate 10 is taken up by a take-up roll 105. In FIG. 2, the void layer 21 of the laminate is covered and protected by a protective sheet unwound from a roll 106. Here, instead of the protective sheet, another layer formed from a long film may be laminated on the void layer 21.
[0226] An example of a coating device for the microgravure method (microgravure coating method) and a method for forming the void layer using the same are shown in Fig. 3. Although the drawing is a cross-sectional view, hatching has been omitted for ease of viewing.
[0227] As shown in the figure, each step in the method using this apparatus is performed while transporting the substrate 10 in one direction by rollers, similar to Fig. 2. The transport speed is not particularly limited and is, for example, 1 to 100 m / min, 3 to 50 m / min, or 5 to 30 m / min.
[0228] First, a coating step (1) is performed in which a sol particle liquid 20'' is applied to the substrate 10 while the substrate 10 is being fed from a feed roller 201 and conveyed. The sol particle liquid 20'' is applied using a liquid reservoir 202, a doctor (doctor knife) 203, and a microgravure 204, as shown in the figure. Specifically, the sol particle liquid 20'' stored in the liquid reservoir 202 is attached to the surface of the microgravure 204, and then the sol particle liquid 20'' is applied to the surface of the substrate 10 by the microgravure 204 while controlling the thickness to a predetermined value by the doctor 203. Note that the microgravure 204 is merely an example and is not limited thereto, and any other coating means may be used.
[0229] Next, the drying step (2) is performed. Specifically, as shown in the figure, the substrate 10 coated with the sol particle liquid 20'' is transported into the oven zone 210, and the sol particle liquid 20'' is dried by heating using the heating means 211 in the oven zone 210. The heating means 211 may be the same as that in FIG. 2, for example. Also, for example, the oven zone 210 may be divided into a plurality of sections to divide the drying step (2) into a plurality of steps, and the drying temperature may be increased in the later drying steps. After the drying step (2), the chemical treatment step (3) is performed in the chemical treatment zone 220. In the chemical treatment step (3), for example, when the dried coating film 20' contains a photoactive catalyst, the substrate 10 is irradiated with light using lamps (light irradiation means) 221 arranged above and below the substrate 10. Alternatively, for example, when the dried coating film 20' contains a thermally activated catalyst, hot air blowers (heating means) are used instead of the lamps (light irradiation devices) 221, and the substrate 10 is heated by the hot air blowers (heating means) 221 arranged above and below the substrate 10. This crosslinking process causes chemical bonding between the pulverized materials in the coating film 20', and the void layer 20 is formed.
[0230] After the chemical treatment step (3), a tacky adhesive layer coating step (tacky adhesive layer forming step) (4) is performed in the tacky adhesive layer coating zone 230a, in which a tacky adhesive or adhesive is applied (coated) onto the porous layer 20 by a tacky adhesive layer coating means 231a to form a tacky adhesive layer 30. Also, as described above, instead of applying (coating) the tacky adhesive or adhesive, a tacky adhesive tape or the like having the tacky adhesive layer 30 may be attached (attached).
[0231] Furthermore, an intermediate layer forming step (aging step) (5) is performed in the intermediate layer forming zone (aging zone) 230, and the void layer 20 and the adhesive layer 30 are reacted to form the intermediate layer 22. As described above, in this step, the void layer 20 becomes the void layer 21 having improved strength. The intermediate layer forming step (aging step) (5) may be performed, for example, by heating the void layer 20 and the adhesive layer 30 using hot air blowers (heating means) 231 arranged above and below the substrate 10. The heating temperature, time, etc. are not particularly limited, but are, for example, as described above.
[0232] Then, after the intermediate formation step (aging step) (5), the laminate film in which the void layer 21 is formed on the substrate 10 is taken up by a take-up roll 251. Thereafter, for example, another layer may be laminated on the laminate film. Also, before the laminate film is taken up by the take-up roll 251, for example, another layer may be laminated on the laminate film. EXAMPLES
[0233] Next, examples of the present invention will be described, but the present invention is not limited to the following examples.
[0234] In the following Reference Examples, Examples, and Comparative Examples, the number of parts (relative amount used) of each substance is by mass (parts by weight) unless otherwise specified.
[0235] In the following Reference Examples, Examples and Comparative Examples, the storage modulus of the adhesive layer at 23°C, the gel fraction of the adhesive layer, the thickness of each layer and the weight average molecular weight of the sol fraction of the adhesive layer were measured by the following measurement methods.
[0236] (Method for measuring storage modulus) The storage modulus of the adhesive layer at 23°C was measured by the following method using a viscoelasticity measuring device ARES (trade name of TA Instruments). That is, first, a sheet (layer) was formed that was the same as the adhesive layer in each of the following Reference Examples, Examples, and Comparative Examples except that it was a sheet with a thickness of 2 mm. The sheet was punched out to fit a parallel plate with a diameter of 25 mm to obtain a measurement sample. The measurement sample was attached to the chuck of the viscoelasticity measuring device ARES. Then, the temperature was increased from -70°C to 150°C at a heating rate of 5°C / min while applying a strain at a cycle of 1 Hz, and the storage modulus at 23°C was measured.
[0237] (Method of measuring gel fraction of adhesive layer) Measurement samples (each pressure-sensitive adhesive composition was applied and then heated and dried) were prepared in the same manner as the pressure-sensitive adhesive layers in the following Reference Examples, Examples, and Comparative Examples. The measurement samples (initial weight W1) were immersed in ethyl acetate and left at room temperature for one week, after which the insoluble matter was removed, and the dried weight (W2) was measured, and the gel fraction was calculated based on the following formula (II). Gel fraction (weight%)=(W2 / W1)×100 (II)
[0238] In the adhesive layers in the following Reference Examples, Examples, and Comparative Examples, it is assumed that the polymer (acrylic polymer) is crosslinked by the crosslinking agent through heating and drying the applied adhesive, thereby forming a crosslinked structure, but the crosslinked structure has not been confirmed.
[0239] (Thickness measurement method) The measurement was performed using a dial gauge.
[0240] (Method for measuring weight average molecular weight of sol component of adhesive layer) From the molecular weight distribution curve measured by gel permeation chromatography (GPC), the weight average molecular weight of the sol and the ratio (weight percentage) of low molecular weight components having a molecular weight of 10,000 or less were calculated. Specifically, first, a measurement sample (after coating with each adhesive composition and drying by heating) was prepared in the same manner as the adhesive layer in each of the following reference examples, examples, and comparative examples. 10 ml of tetrahydrofuran (THF) was added to 200 mg of this measurement sample, and the mixture was left to stand for 20 hours and filtered through a 0.45 μm membrane filter. Thereafter, the obtained filtrate was subjected to GPC measurement using the following measurement device and measurement conditions, and the weight average molecular weight of the sol and the ratio (weight percentage) of low molecular weight components having a molecular weight of 10,000 or less were calculated from the molecular weight distribution curve as described above. GPC measuring device: Product name "AQCUITY APC" (manufactured by Water) Column: Product name "G7000HxL+GMHxL+GMHxL" (manufactured by Tosoh Corporation) Eluent: tetrahydrofuran (THF) Flow rate: 0.8mL / min Detector: Differential refractometer (RI) Column temperature (measurement temperature): 40℃ Injection volume: 100μL Standard: Polystyrene
[0241] [Reference Example 1: Production of coating solution for forming void layer] First, a gel having a porous structure (a silicone porous body) was produced by gelling the silicon compound (step (1) below) and aging (step (2) below). After that, the following steps (3) morphology control step, (4) solvent replacement step, and (5) gel crushing step were performed to obtain a coating liquid for forming a void layer (liquid containing gel crushed material). In this reference example, the following step (3) morphology control step was performed as a separate step from the following step (1) as described below. However, the present invention is not limited to this, and for example, the following step (3) morphology control step may be performed during the following step (1).
[0242] (1) Gelation of silicon compounds 9.5 kg of MTMS, a precursor of a silicon compound, was dissolved in 22 kg of DMSO. 5 kg of 0.01 mol / L oxalic acid solution was added to the mixture, and the mixture was stirred at room temperature for 120 minutes to hydrolyze MTMS and generate tris(hydroxy)methylsilane.
[0243] 3.8 kg of 28% ammonia water and 2 kg of pure water were added to 55 kg of DMSO, and the hydrolyzed mixture was then added and stirred at room temperature for 60 minutes. The liquid after stirring for 60 minutes was poured into a stainless steel container measuring 30 cm in length, 30 cm in width, and 5 cm in height and allowed to stand at room temperature to gel tris(hydroxy)methylsilane and obtain a gel-like silicon compound.
[0244] (2) Aging process The gel-like silicon compound obtained by the gelation treatment was incubated at 40°C for 20 hours to perform aging treatment, and the rectangular solid-shaped lump gel was obtained. Since the amount of DMSO (a high-boiling point solvent with a boiling point of 130°C or higher) used in the raw material was about 83% by weight of the entire raw material, it was clear that this gel contained 50% by weight or more of a high-boiling point solvent with a boiling point of 130°C or higher. Furthermore, since the amount of MTMS (a monomer that is a constituent unit of the gel) used in the raw material was about 8% by weight of the entire raw material, it was clear that the content of a solvent (methanol in this case) with a boiling point of less than 130°C generated by hydrolysis of the monomer (MTMS), which is a constituent unit of the gel, was 20% by weight or less.
[0245] (3) Morphology control process Water, which was a replacement solvent, was poured onto the gel synthesized in the 30 cm × 30 cm × 5 cm stainless steel vessel by the steps (1) and (2). Next, the cutting blade of a cutting tool was slowly inserted into the gel from above in the stainless steel vessel, and the gel was cut into a rectangular parallelepiped with a size of 1.5 cm × 2 cm × 5 cm.
[0246] (4) Solvent replacement process Next, a solvent substitution step was carried out as follows (4-1) to (4-3).
[0247] (4-1) After the "(3) morphology control step", the gel silicon compound was immersed in water of 8 times the weight of the gel silicon compound, and slowly stirred for 1 hour so that only the water was circulated. After 1 hour, the water was replaced with the same amount of water, and further stirred for 3 hours. After that, the water was replaced again, and then heated at 60°C for 3 hours while slowly stirring.
[0248] (4-2) After (4-1), the water was replaced with isopropyl alcohol in an amount four times the weight of the gel silicon compound, and the mixture was heated at 60° C. for 6 hours while stirring.
[0249] (4-3) After (4-2), the isopropyl alcohol was replaced with the same weight of isobutyl alcohol, and the mixture was heated at 60°C for 6 hours to replace the solvent contained in the gel-like silicon compound with isobutyl alcohol. In this manner, the gel for producing a gap layer of the present invention was produced.
[0250] (5) Gel crushing process The gel (gel-like silicon compound) after the solvent replacement step (4) was subjected to two stages of pulverization: continuous emulsification dispersion (Milder MDN304, manufactured by Pacific Machinery Co., Ltd.) in the first pulverization stage, and high-pressure medialess pulverization (Starburst HJP-25005, manufactured by Sugino Machine Co., Ltd.). In this pulverization process, 26.6 kg of isobutyl alcohol was added to 43.4 kg of the gel containing the solvent-substituted gel-like silicon compound, and then weighed. The first pulverization stage was pulverized for 20 minutes by circulation pulverization, and the second pulverization stage was pulverized at a pulverization pressure of 100 MPa. In this way, an isobutyl alcohol dispersion (containing gel pulverized product) in which nanometer-sized particles (pulverized product of the gel) were dispersed was obtained. Furthermore, 224 g of a 1.5% solution of WPBG-266 (trade name, manufactured by Wako) in methyl isobutyl ketone was added to 3 kg of the gel powder-containing liquid, and then 67.2 g of a 5% solution of bis(trimethoxysilyl)ethane (manufactured by TCI) in methyl isobutyl ketone was added, and then 31.8 g of N,N-dimethylformamide was added and mixed to obtain a coating liquid.
[0251] In the above manner, a coating liquid (containing pulverized gel) for forming a void layer of this reference example (reference example 1) was produced. The peak pore diameter of the pulverized gel (microporous particles) in the coating liquid (containing pulverized gel) for forming a void layer was measured by the above-mentioned method and was found to be 12 nm.
[0252] [Reference Example 2: Formation of adhesive layer] The adhesive layer of this Reference Example (Reference Example 2) was formed by the following procedures (1) to (3).
[0253] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 90.7 parts of butyl acrylate, 6 parts of N-acryloylmorpholine, 3 parts of acrylic acid, 0.3 parts of 2-hydroxybutyl acrylate, and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 g of ethyl acetate. Next, nitrogen gas was introduced while gently stirring the contents in the four-neck flask to replace the atmosphere with nitrogen. Thereafter, the liquid temperature in the four-neck flask was kept at around 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0254] (2) Preparation of acrylic adhesive composition An acrylic adhesive composition (acrylic adhesive solution) was prepared by blending 0.2 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.3 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Co., Ltd.), and 0.2 parts of γ-glycidoxypropylmethoxysilane (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0255] (3) Formation of adhesive layer The acrylic adhesive composition obtained in (2) above was applied to one side of a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Corporation, thickness: 38 μm) so that the adhesive layer would have a thickness of 12 μm after drying, and dried at 150° C. for 3 minutes to form an adhesive layer (tacky adhesive layer). The storage modulus G' of this adhesive layer (tacky adhesive layer) at 23° C. was 1.3×10 5 It was.
[0256] [Reference Example 3: Formation of adhesive layer] The adhesive layer of this reference example (Reference Example 3) was formed by the following procedures (1) to (3).
[0257] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 96.9 parts of butyl acrylate, 3 parts of acrylic acid, 0.1 parts of 2-hydroxyethyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 g of ethyl acetate. Next, nitrogen gas was introduced to replace the nitrogen gas while gently stirring the contents in the four-neck flask. Thereafter, the liquid temperature in the four-neck flask was kept at around 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0258] (2) Preparation of acrylic adhesive composition A solution of an acrylic adhesive composition was prepared by blending 0.5 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.2 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Co., Ltd.), and 0.2 parts of γ-glycidoxypropylmethoxysilane (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0259] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Corporation, thickness: 38 μm) so that the adhesive layer would have a thickness of 20 μm after drying, and was dried at 150° C. for 3 minutes to form an adhesive layer (tacky adhesive layer). The storage modulus G' of this adhesive layer (tacky adhesive layer) at 23° C. was 1.1×10 5 It was.
[0260] [Reference Example 4: Formation of adhesive layer] The adhesive layer of this reference example (Reference Example 4) was formed by the following procedures (1) to (3).
[0261] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 77 parts of butyl acrylate, 20 parts of phenoxyethyl acrylate, 2 parts of N-vinyl-2-pyrrolidone, 0.5 parts of acrylic acid, 0.5 parts of 4-hydroxybutyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 parts of ethyl acetate. Next, nitrogen gas was introduced while gently stirring the contents in the four-neck flask to replace the atmosphere with nitrogen. Thereafter, the liquid temperature in the four-neck flask was kept at about 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0262] (2) Preparation of acrylic adhesive composition A solution of an acrylic pressure-sensitive adhesive composition was prepared by blending 100 parts of the solid content of the acrylic polymer solution obtained in (1) above with 0.1 part of an isocyanate crosslinking agent (Takenate D160N, manufactured by Mitsui Chemicals, Inc.; trimethylolpropane hexamethylene diisocyanate), 0.3 part of benzoyl peroxide (Niper BMT, manufactured by Nippon Oil & Fats Corporation), and 0.2 part of γ-glycidoxypropyl methoxysilane (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0263] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a polyethylene terephthalate film (separator film: Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") treated with a silicone release agent, and dried at 150°C for 3 minutes to form an adhesive layer (adhesive layer) with a thickness of 20 μm on the surface of the separator film. The storage modulus G' of this adhesive layer (adhesive layer) at 23°C was 1.1×10 5 It was.
[0264] [Reference Example 5: Formation of adhesive layer] The adhesive layer of this reference example (Reference Example 5) was formed by the following procedures (1) to (3).
[0265] (1) Preparation of prepolymer composition A monomer mixture consisting of 68 parts of 2-ethylhexyl acrylate, 14.5 parts of N-vinyl-2-pyrrolidone, and 17.5 parts of 2-hydroxyethyl acrylate was mixed with 0.035 parts of a photopolymerization initiator (trade name "Irgacure 184", BASF) and 0.035 parts of a photopolymerization initiator (trade name "Irgacure 651", BASF), and then irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa s, to obtain a prepolymer composition in which some of the monomer components were polymerized.
[0266] (2) Preparation of acrylic adhesive composition 0.150 parts of hexanediol diacrylate (HDDA) and 0.3 parts of a silane coupling agent (product name "KBM-403", Shin-Etsu Chemical Co., Ltd.) were added to and mixed with the prepolymer composition obtained in (1) above to obtain an acrylic pressure-sensitive adhesive composition.
[0267] (3) Formation of adhesive layer The acrylic adhesive composition obtained in (2) was applied to one side of a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Corporation, thickness: 50 μm) so that the thickness of the adhesive layer after drying would be 25 μm, and a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Corporation, thickness: 38 μm) was further provided on the coating layer to cover the coating layer and block oxygen. Next, this laminate was irradiated with ultraviolet light at an illuminance of 5 mW / cm2 from a black light (manufactured by Toshiba) from the upper surface (MRF38 side) of the laminate for 300 seconds. Further, a drying process was performed in a dryer at 90 ° C. for 2 minutes to volatilize the remaining monomer and form an adhesive layer (adhesive layer). The storage modulus G' of this adhesive layer (adhesive layer) at 23 ° C. was 1.1 × 10 5 It was.
[0268] [Reference Example 6: Formation of adhesive layer] The adhesive layer of this reference example (Reference Example 6) was formed by the following procedures (1) to (3).
[0269] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 99 parts of butyl acrylate, 1 part of 4-hydroxybutyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 parts of ethyl acetate. Next, nitrogen gas was introduced into the contents of the four-neck flask while gently stirring the contents to replace the atmosphere with nitrogen. Thereafter, the liquid temperature in the four-neck flask was kept at about 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0270] (2) Preparation of acrylic adhesive composition A solution of an acrylic pressure-sensitive adhesive composition was prepared by blending 0.1 part of an isocyanate crosslinking agent (manufactured by Mitsui Takeda Chemical Co., Ltd. under the trade name "Takenate D110N", trimethylolpropane xylylene diisocyanate), 0.1 part of benzoyl peroxide (manufactured by Nippon Oil & Fats Co., Ltd. under the trade name "Niper BMT"), and 0.2 parts of γ-glycidoxypropyl methoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd. under the trade name "KBM-403") with 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0271] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a polyethylene terephthalate film (separator film: Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") treated with a silicone release agent, and dried at 150°C for 3 minutes to form an adhesive layer (tacky adhesive layer) with a thickness of 20 μm on the surface of the separator film. The storage modulus G' of this adhesive layer (tacky adhesive layer) at 23°C was 8.2×10 4 It was.
[0272] Reference Example 7: Formation of adhesive layer The adhesive layer of this reference example (Reference Example 7) was formed by the following procedures (1) to (3).
[0273] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 90.7 parts of butyl acrylate, 6 parts of N-acryloylmorpholine, 3 parts of acrylic acid, 0.3 parts of 2-hydroxybutyl acrylate, and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 g of ethyl acetate. Next, nitrogen gas was introduced while gently stirring the contents in the four-neck flask to replace the atmosphere with nitrogen. Thereafter, the liquid temperature in the four-neck flask was kept at about 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0274] (2) Preparation of Acrylic Adhesive Composition An acrylic adhesive composition (acrylic adhesive solution) was prepared by blending 0.15 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.2 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Corporation), and 0.2 parts of γ-glycidoxypropylmethoxysilane (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0275] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a polyethylene terephthalate film (separator film: Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") treated with a silicone release agent, and dried at 150°C for 3 minutes to form an adhesive layer (adhesive layer) with a thickness of 75 µm on the surface of the separator film. The storage modulus G' of this adhesive layer (adhesive layer) at 23°C was 1.0 x 10 5 It was.
[0276] Reference Example 8: Formation of adhesive layer The adhesive layer of this reference example (Reference Example 8) was formed by the following procedures (1) to (3).
[0277] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 95 parts of butyl acrylate, 5 parts of acrylic acid, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 g of ethyl acetate. Next, nitrogen gas was introduced to replace the nitrogen gas while gently stirring the contents in the four-neck flask. Thereafter, the liquid temperature in the four-neck flask was kept at about 55°C and a polymerization reaction was carried out for 8 hours, after which the liquid temperature in the flask was raised to 70°C and a reaction was carried out for 2 hours to prepare an acrylic polymer solution.
[0278] (2) Preparation of Acrylic Pressure-Sensitive Adhesive Composition 0.7 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.2 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Corporation), and 0.2 parts of γ-glycidoxypropylmethoxysilane (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed with 100 parts of the solid content of the acrylic polymer solution obtained in (1) above to prepare a solution of an acrylic pressure-sensitive adhesive composition.
[0279] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a polyethylene terephthalate film (separator film: Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") treated with a silicone release agent, and dried at 150°C for 3 minutes to form an adhesive layer (adhesive layer) with a thickness of 75 µm on the surface of the separator film. The storage modulus G' of this adhesive layer (adhesive layer) at 23°C was 7.7 x 10 4 It was.
[0280] [Example 1] The high porosity layer-forming coating liquid prepared in Reference Example 1 was applied to an acrylic substrate and dried to form a porous layer with a thickness of about 850 nm (porosity: 59% by volume). Next, UV irradiation (300 mJ) was performed from the porous layer surface. Thereafter, the adhesive with a thickness of 12 μm obtained in Reference Example 2 was attached to the porous layer surface, and aging was performed at 60° C. for 20 hours to produce the laminate of this example.
[0281] Furthermore, the laminate of this embodiment produced as described above was placed in an oven at 85°C and 85% RH, and a heat and humidity durability test was performed for 500 hours. The degree of filling of the voids in the void layer after the heat and humidity durability test was confirmed by SEM, and the remaining porosity was calculated. The results are shown in Table 1.
[0282] [Example 2] The laminate of this example was produced in the same manner as in Example 1, except that the adhesive obtained in Reference Example 3 was used instead of the adhesive in Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0283] [Example 3] The laminate of this example was produced in the same manner as in Example 1, except that the adhesive obtained in Reference Example 4 was used instead of the adhesive in Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0284] [Example 4] The laminate of this example was produced in the same manner as in Example 1, except that the adhesive obtained in Reference Example 5 was used instead of the adhesive in Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0285] [Example 5] A laminate of this example was produced in the same manner as in Example 1, except that the thickness of the adhesive layer formed with the adhesive of Reference Example 2 was 5 μm. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0286] [Example 6] The same procedure as in Example 1 was repeated, except that the adhesive obtained in Reference Example 7 was used instead of the adhesive in Reference Example 2. The laminate of this example was produced by carrying out the same procedure as in Example 1. A humidity durability test was conducted and the remaining porosity was calculated. The results are shown in Table 1.
[0287] [Comparative Example 1] A laminate of this comparative example was produced in the same manner as in Example 1, except that the adhesive obtained in Reference Example 6 was used instead of the adhesive in Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0288] [Comparative Example 2] A laminate of this comparative example was produced in the same manner as in Example 1, except that an epoxy adhesive semi-cured by UV (ultraviolet radiation) was used instead of the adhesive of Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0289] [Comparative Example 3] A laminate of this comparative example was produced in the same manner as in Example 1, except that the adhesive obtained in Reference Example 8 was used instead of the adhesive in Reference Example 2. Furthermore, a heat and humidity durability test was carried out in the same manner as in Example 1, and the residual porosity was calculated. The results are shown in Table 1.
[0290] The adhesive strength of each of the laminates of Examples 1 to 6 and Comparative Examples 1 to 3 was measured by the above-mentioned measuring method. The storage modulus of the adhesive layer at 23°C, the gel fraction of the adhesive layer, the thickness of the intermediate layer, the thickness of the adhesive layer, and the weight average molecular weight of the sol fraction of the adhesive layer were also measured by the above-mentioned measuring method. Furthermore, the void areas were binarized from the SEM image of the laminate after the durability test, and the void residual rate was calculated. The results are also shown in Table 1.
[0291] [Table 1]
[0292] As shown in Table 1, the laminates of Examples 1 to 6 were able to achieve both adhesive strength and resistance to penetration of the adhesive (adhesive layer) into voids. In contrast, in the laminates of Comparative Examples 1 to 3, the adhesive (adhesive layer) penetrated into the voids in the void layer, and the void remaining rate of the void layer after the durability test was low. [Industrial Applicability]
[0293] As described above, according to the present invention, it is possible to provide a laminate of a void layer and a tacky adhesive layer, an optical member, and an optical device that achieve both adhesive strength or bonding strength and the difficulty of the adhesive or adhesive penetrating into the void. The use of the present invention is not particularly limited. For example, the optical device of the present invention is not particularly limited, and examples thereof include image display devices and lighting devices. Examples of the image display devices include liquid crystal displays, organic EL displays, micro LED displays, and the like. Examples of the lighting devices include organic EL lighting, and the like. Furthermore, the use of the laminate of the present invention is not limited to the optical member and optical device of the present invention, and is arbitrary, and can be used for a wide range of uses. [Explanation of symbols]
[0294] 10 Base material 20 void layer 20' Coating film (after drying) 20'' Sol Particle Liquid 21 Improved strength of the void layer 22 Middle Class 30 Adhesive layer 101 Delivery roller 102 Coating roll 110 Oven Zone 111 Hot air heater (heating means) 120 Chemical Treatment Zone 121 Lamp (light irradiation means) or hot air heater (heating means) 130a Adhesive layer coating zone 130 Intermediate formation zone 131a Adhesive layer coating means 131 Hot air heater (heating means) 105 Winding roll 106 rolls 201 Feed roller 202 Liquid Reservoir 203 Doctor (Doctor Knife) 204 Microgravure 210 Oven Zone 211 Heating means 220 Chemical Treatment Zone 221 Light irradiation means or heating means 230a Adhesive layer coating zone 230 Intermediate formation zone 231a Adhesive layer coating method 231 Hot air heater (heating means) 251 Winding Roll
Claims
1. A void layer, an adhesive layer, and an intermediate layer formed by integrating a part of the void layer and a part of the adhesive layer, The void layer has an open-cell structure having a continuous pore structure, The porosity of the void layer is 35 volume% or more, the pressure-sensitive adhesive layer is formed of a pressure-sensitive adhesive containing a (meth)acrylic polymer and a crosslinking agent, The storage modulus of the adhesive layer at 23° C. is 1.0×10 5 Pa or more, The adhesive layer has a gel fraction of 70% or more, A laminate characterized in that, in a molecular weight measurement of the adhesive layer by gel permeation chromatography, the content of low molecular weight components having a molecular weight of 10,000 or less in the sol fraction of the adhesive layer is 20 weight % or less.
2. 2. The laminate according to claim 1, wherein the weight average molecular weight of the sol component of the adhesive layer is 500,000 or less.
3. The laminate described in claim 1, wherein the (meth)acrylic polymer is a (meth)acrylic polymer obtained by polymerizing a monomer component containing (meth)acrylic acid as a monomer component.
4. 4. The laminate according to claim 3, wherein the (meth)acrylic polymer is a (meth)acrylic polymer obtained by polymerizing a monomer component containing 0.5 to 5% by weight of the (meth)acrylic acid.
5. 5. The laminate according to claim 3, wherein the (meth)acrylic polymer is a (meth)acrylic polymer obtained by polymerizing a monomer component containing a hydroxyalkyl (meth)acrylate.
6. 6. The laminate according to claim 5, wherein the monomer component contains 0.05 to 2% by weight of the hydroxyalkyl (meth)acrylate.
7. 2. The laminate according to claim 1, wherein after a heat and humidity durability test in which the laminate is maintained at a temperature of 85° C. and a relative humidity of 85% for 500 hours, the residual void ratio of the porous layer is 50% by volume or more before the heat and humidity durability test.
8. 8. The laminate according to claim 7, wherein the void remaining rate of the void layer after the heat and humidity durability test is more than 50% and not more than 99% of the void remaining rate when only the void layer is subjected to the heat and humidity durability test.
9. The laminate according to claim 1 , wherein the intermediate layer has a thickness of 200 nm or less.
10. A laminate described in any one of claims 1 to 9, wherein after a heat and humidity durability test in which the intermediate layer is maintained at a temperature of 85°C and a relative humidity of 85% for 500 hours, the increase in thickness of the intermediate layer is 500% or less compared to the thickness of the intermediate layer before the heat and humidity durability test.
11. the pressure-sensitive adhesive layer is formed of a pressure-sensitive adhesive containing a (meth)acrylic polymer and a crosslinking agent, The thickness of the adhesive layer is 2 to 50 μm, The laminate according to claim 1 , wherein the adhesive layer satisfies the following formula (I): [(100-X) / 100]×Y≦10 (I) In the formula (I), X is the gel fraction (%) of the adhesive layer, Y is the thickness (μm) of the adhesive layer.
12. 3. The laminate according to claim 1, wherein the weight average molecular weight of the sol component of the adhesive layer is from 50,000 to 500,000.
13. The laminate according to claim 1 , wherein in the adhesive layer, the (meth)acrylic polymer is crosslinked with the crosslinking agent to form a crosslinked structure.
14. 14. The laminate according to claim 1, wherein the refractive index of the air gap layer is 1.25 or less.
15. The laminate according to claim 1 , wherein the adhesive layer is formed from an optical acrylic adhesive having a total light transmittance of 85% or more and a haze of 3% or less.
16. An optical member comprising the laminate according to claim 1 .
17. An optical device comprising the optical member according to claim 16.
Citation Information
Patent Citations
Surface light-emitting device and manufacture thereof
JP1998062626A
Backlight panel, light guide plate, reflection plate, and adhesive sheet
JP2012156082A
Pressure-sensitive adhesive composition, pressure-sensitive adhesive and pressure-sensitive adhesive sheet
JP2014152317A
Optical laminate, method for manufacturing optical laminate, optical member, image display device, method for manufacturing optical member and method for manufacturing image display device
JP2017047677A
polymer components
JP2019512560A